Energy input: The physical essence of electrorheological structural behaviors in waxy crude oil - Hongying Li; Chaoyue Zhang; Jiabao Kang; Yiwei Xie; Qibing Li; Yang Su; Quande Li; Yichen Wei; Jinjun Zhang (Fuel, 2027)

Deep eutectic solvents as a versatile platform for wood modification: Lignocellulosic regulation and functional applications - Yichen Hua; Tongtong Li; Xinyou Liu; Jianing Li (Bioresource Technology, 2027)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

High-accuracy EEG-based driver fatigue detection using feature-coupled tensor decomposition for multimodal brain connectivity analysis - Tian Yan; Hechong Su; Zengyao Yang; Aimin Zhang; Yidan Ma; Xiaolong Wang; Yue Wu; Li Yan; Yichen Wang; Jianfu Cao (Cognitive Neurodynamics, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Co-valorization of lignin and waste polyethylene terephthalate (PET) via Fe/β-zeolite-catalyzed tandem depolymerization - Chang Li; Shihai Yang; Hongzhi Luo; Haiping Chen; Yishuang Wang; Yichen Chen; Chuannan Nie; Defang Liang; Mingqiang Chen (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Energy-efficient electrochemical ammonia removal enabled by replacing hydrogen evolution with four-electron oxygen reduction at the cathode - Zeyu Du; Yongyang Chen; Xiaowei An; Changhui Zhou; Yaobin Wang; Chaoyue Xie; Ruiqing Zhao; Zhiyuan Su; Zhinan Dai; Yichen Gong; Guanjun Qu; Fangzhou Li; et al. (Water Research, 2026)

Diverse and ultraviolet-inducible phage-associated antibiotic resistance genes in wastewater treatment plants - Yichen Huang; Peng Liu; Jinghan Wu; Jie Li; Jinhua Tuo; Qifeng Zhang; Xu-Xiang Zhang (Water Research, 2026)

Physics-informed operator learning for rapid hydrograph-to-field prediction on an unstructured-mesh flood benchmark - Yichen Li; Qiang Ye; Shanliang Zhang; Tiechui Liu; Lingzao Zeng (Journal of Hydrology, 2026)

Complexation mechanism of pectins with varying esterification degrees and pea protein isolate: Effects on protein solubility, emulsifying properties, and emulsion stability - Ying Kuang; Tao Wang; Jiapeng Wu; Huiyu Liu; Yichen Yang; Kai Chen; Bo Peng; Yi Liu; Qian Zhang; Fatang Jiang; Kao Wu; Jia Liu; et al. (Journal of Food Engineering, 2026)

β-globin mediates antimicrobial defense and inflammatory regulation in common carp (Cyprinus carpio) - Xiuying Cui; Chenfan Zhao; Zhaohui Jin; Yichen Liu; Li Li; Xianliang Zhao; Xianghui Kong (Fish & Shellfish Immunology, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

The AtRNC1-AtWTF1 protein complex is essential for chloroplast group Ⅱ intron splicing, ribosome biogenesis, and embryo development in Arabidopsis - Yichen Zhang; Xinyun Xu; Yajuan Li; Siwen Wei; Jiayi Shen; Qing-Bo Yu; Yong-Lan Cui (Plant Molecular Biology, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Increasing salinity exacerbates the bioaccumulation and toxicity of perfluorooctanoic acid (PFOA) in Manila clams (Ruditapes philippinarum) - Yichen Cao; Shuqi Jiang; Ningning Wu; Zhijun Tan; Chengchen Wu; Qianqian Geng; Fengling Li; Yukun Zhao; Mengmeng Guo (Marine Pollution Bulletin, 2026)

Methylome and transcriptome profiles reveal the importance of glycometabolism in thermal plasticity of large yellow croaker - Yanfei Yang; Yichen Li; Yidi Wu; Baohua Chen; Ji Zhao; Qiaozhen Ke; Weiqiang Zheng; Yun Li; Tao Zhou; Peng Xu; Ning Li (Aquaculture, 2026)

Corrigendum to “Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework” [Sustainable Cities and Society, 143 (2026), 107342] - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Semantic behavioral sequences from UAV video: Decoding the effects of the micro-scale built environment on human behavior in neighborhood centers - Qianyu Liu; Guangtian Zou; Yichen Luo; Wenrui Zhao; Huibao Li (Sustainable Cities and Society, 2026)

Silica nanoparticles disrupt blood–testis barrier integrity in Sertoli cells by inducing inflammation-mediated p38 MAPK pathway - Ying Wang; Wenpeng Liu; Yichen Wang; Dan Chen; Shoufang Jiang; Jinlong Li; Wenxuan Tang; Ping Lu; Xuan Shang (Reproductive Toxicology, 2026)

Geochemical anomaly identification based on ILR-PCA and vision transformer: A case study of the Yangshan Gold Belt, West Qinling, China - Xiulong Chen; Xiuhong Peng; Yuke Tian; Yichen Wu; Hongrui Li; Yazhou Wang; Hai Liu (Journal of Geochemical Exploration, 2026)

6PPD and 6PPD-Q driven phytotoxicity in Eichhornia crassipes: From molecular damages to ecological potential implications - Yichen Ge; Weitao Liu; Xiang Li; Jinzheng Liu; Ruiying Shi; Xinwei Shi; Aurang Zeb; Qi Wang; Jianling Wang; Cuihong Chen; Yuebing Sun (Journal of Environmental Sciences, 2026)

Evolution of PM2.5 chemical composition during summer new particle formation in a coastal city in the yangtze river delta: insights from pollution episodes, machine learning, and air mass origins - Han Zhou; Yichen Lu; Zeyi Li; Honglei Wang; Lijuan Shen; Yue Chen; Deyu Liu; Da Xu (Environmental Research, 2026)

Synthesis of flexible AgNW@SnO2 core-shell networks for transparent EMI shielding and infrared stealth - Tianwei Dong; Yilin Hao; Pengcheng Li; Xingyu Chen; Yichen Li; Dan Xu; Yujing Zhang; Chuyang Liu; Guangbin Ji (Chemical Engineering Journal, 2026)

Vinpocetine attenuates myocardial ischemia/reperfusion injury in mice by suppressing oxidative stress, inflammation, and apoptosis - Tianchen Xia; Yichen Qian; Yilong Jiang; Qiang Zhang; Jiahao Pan; Hui Xiong; Jiaxin Zhang; Taotao Yan; Qi Li; Shenjie Zhang; Qingsheng You (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Peripheral CD4 T-Cell State Remodeling in Migraine Revealed by Single-Cell RNA Sequencing - Quan Feng; Yichen Li; Na Li; Weisheng Zhan; Ge Tan (Journal of Molecular Neuroscience, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

A rapid optimization framework for high-rise office block design elements driven by carbon emission performance: Perspectives from three climate zones in China - Shen Xu; Qiuguo He; Tao Luo; Yichen Dong; Hua Zhong; Junchao Duan; Gaomei Li (Sustainable Cities and Society, 2026)

Dynamic analysis of a mooring system considering embedded chain-seabed interaction using a global-local coupled framework - Kejiang Li; Qilin Yin; Xiang Li; Jinjin Zhai; Zhiming Yuan; Yichen Li (Ocean Engineering, 2026)

Threshold responses of runoff-sediment dynamics to hydrological connectivity - Taoxi Li; Qian Zeng; Yichen Yin; Gang Sun; Ruyi Zheng; Yichun Ma; Jiale Ye; Peiyao Xiao; Yaojun Liu (Journal of Hydrology, 2026)

Nitrogen limits microbial carbon use efficiency along soil organic carbon gradients in the Chaobai River Basin, China - Leyun Wang; Fei Chen; Yichen Wu; Mengting Zhu; Guanghe Li; Miao Li (Journal of Environmental Sciences, 2026)

Ternary ZnO@ZIF@COF core-shell-shell heterostructures: Energy-band cascade and layered signal amplification for biogenic amine detection - Junxi Cheng; Ting Li; Chang Liu; Yichen Gong; Xuanjun Wang; Miaomiao Liu; Yueguang Li; Hewei Yang; Zihan Qin; Zhengyang Cheng; Liyuan Cai; Qihua Sun; et al. (Chemical Engineering Journal, 2026)

Abrupt intensification and spatiotemporal dynamics of large-scale harmful algal blooms in China’s marginal seas mapped using multi-sensor satellite imagery and deep learning - Yichen Du; Mengqiu Wang; Zhongbin B. Li; Junsheng Li; Jiaochan Hu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Grapholita molesta V-ATPase D acts as a susceptibility determinant of larvae to Bt Cry2Ab toxin - Yanshen Fu; Xiaoyan Yang; Yicong Wang; Qiangqiang Kang; Donghan Wang; Jiacheng Ye; Yichen Wang; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2026)

Pickering emulsion hydrogels: Fabrication strategies, tailorable properties and multifunctional applications - Juping Zheng; Mengdie Chen; Kaiqing Yang; Chao Li; Yuzhu Song; Yichen Tian (Chemical Engineering Journal, 2026)

Whole-life evolution of soil aggregate structure and nutrient (C-N-P) retention function in terraced citrus orchards - Haiqun Yuan; Wenbin Xie; Yaojun Liu; Faxing Shen; Wenqing Li; Yichen Yin; Jiale Ye; Wuyan Wu; Wanglu Li (CATENA, 2026)

Rigid-flexible coupling errors calibration based on machine learning for robotic harvesting arm in orchard - Yichen Qiao; Qingchun Feng; Liping Chen; Congju Shen; Wenqiao Lu; Yajun Li; Yuhang Ma; Hongwen Li (Computers and Electronics in Agriculture, 2026)

Yeast-based β-glucan oral carriers for targeted delivery of bioactive compounds: Enabling precision nutrition intervention - Yannan Chen; Yuanyuan Liu; Wenjin Han; Yichen Huang; Yukun Song; Dapeng Li; Mingqian Tan (Trends in Food Science & Technology, 2026)

Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

The G143S substitution of cytochrome b confers field resistance to pyraclostrobin in Glomerella cingulata - Xushi Jiang; Qian Yang; Yibo Man; Yichen Ma; Yujie Lu; Na Liu; Caixia Wang; Sen Lian; Baohua Li; Weichao Ren (Pesticide Biochemistry and Physiology, 2026)

The fate of exogenous organic matter on ferrihydrite: Critical controls of saturation on carbon and nitrogen sequestration - Fei Chen; Yichen Wu; Leyun Wang; Mengting Zhu; Rui Liu; Xiang Liu; Guanghe Li; Miao Li (Journal of Environmental Management, 2026)

High-Efficient synthesis of coal-based few-layer graphene by laser-induced: Regulation mechanism of coal maceral groups - Xiao Ma; Shaoqing Wang; Jingzhe Zhang; Yichen Mi; Xinyuan Song; Shanshan Lu; Xiaoguang Li (Fuel, 2026)

The synergistic effects of multiple urban morphological factors on building and residential travel carbon emissions at the neighborhood scale - Yuchen Qin; Yuchen Xie; Yichen Dong; Qi Zhang; Xiaoping Li; Qiwei Chen; Minghao Wang; Shen Xu (Energy and Buildings, 2026)

Does Water Vapor from Natural Gas Combustion Worsen Air Quality? Reassessing the Impact of Coal-to-Gas Switching on Winter Haze in Northern China - Siyue Yang; Yichen Wang; Xia Li; Lang Liu (Atmospheric Environment, 2026)

Research advances on Cordyceps sinensis and its components in relation to omics biomarkers for the neurological disorders - Zeyu Lai; Biqin Zhang; Zixuan Fu; Rusong Li; Yichen Qian; Yang Zhang; Peng Xu; Yaoqiang Du (The Science of Nature, 2026)

Features, impacts and identification of DNA damage in ancient microbes - Liwen Yang; Kexin Li; Yichen Liu; Qiaomei Fu (Science China Earth Sciences, 2026)

Assessment and simulation of carbon storage in high-groundwater coal basins based on detailed water body classification: a case study of the Yanzhou Coalfield, China - Yanan He; Yanhua Fu; Li Wang; Wenqi Chen; Wu Xiao; Yichen Shi; Zhengshan Ju (Environmental Monitoring and Assessment, 2026)

The flexible metabolism of Accumulibacter and prevalence of clade IIC due to nitrite stress in a denitrifying phosphorus removal sludge - Juan Ma; Haidong Jin; Wengqing Tian; Peng Wan; Yichen Zhang; Zhe Li; Yujun Guo; Xinyao Ma; Peng Wang; Xiaojun Yu (Process Safety and Environmental Protection, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Isolation, characterization and biotechnological potential of a contaminant-derived cyanobacterium Sodalinema sp. ZYS - Yang Zhao; Zhichao Zhang; Yue Qiao; Yichen Li; Xiang Liu; Yan Liu; Tao Zhu; Xuefeng Lu (Bioresource Technology, 2026)

High-titer de novo raspberry ketone production in Yarrowia lipolytica via precursor supply engineering and fed-batch fermentation optimization - Yuanyuan Li; Shuhao Niu; Zixuan Wang; Yichen Wang; Xiaojuan Zhang; Yu Deng; Shenghu Zhou (Bioresource Technology, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

A framework to identify winter fallow arable lands through machine learning methods - Dan Li; Wenzuo Zhou; Yichen Hu; Xinyu Yao (Advances in Space Research, 2026)

Plant patches maintain soil nematode abundance and energy flow but not community structure in severely-degraded alpine grasslands in the Qinghai-Tibetan Plateau - Jie Wen; Tao Liu; Xiaoli Wang; Junjie Lei; Chunhui Zhang; Zhilei Li; Yichen Xu; Yuan Ma; Buqing Zhong; Xiaocui Liang; Wende Yan; Yushou Ma; et al. (Journal of Environmental Management, 2026)

Low-carbon renovation of old residential blocks: An envelope-focused assessment framework for carbon reduction effects and economic benefits - Shen Xu; Yichen Dong; Hongxin Guo; Zhen Yu; Bo Pan; Congyue Qi; Gaomei Li (Energy and Buildings, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Overexpression of miR-195-5p Suppresses Gastric Cancer Progression by Regulating LAMP2-Mediated Autophagy - Chenglong Shen; Fang Zhou; Xiaolei Zhang; Jiazhe Shao; Yuchao Wang; Haichen Liu; Yichen Li; Guoqiang Zhou; Zhiliang Shi (Biochemical Genetics, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Emission reduction optimization of recycling pathways for retired photovoltaic modules in China: A coupled model of life cycle assessment and evolutionary game theory - Xu Zhu; Yichen Li; Yue Zhang; Yuanyuan Sun; Wen Xu; Lu Bai (Journal of Cleaner Production, 2026)

Information content analysis of venus clouds and haze based on polarization bands of the SPICAV IR and Venspec-H instruments - Yiqi Li; Xiaobing Sun; Xiao Liu; Honglian Huang; Xiaobing Zheng; Yichen Wei; Yizhe Fan; Shun Yao (Icarus, 2026)

From strong to switchable adhesion: Gecko-inspired design strategies and practical applications - Changlin Shen; Weimin Heng; Chunxiao Wu; Xinrui Hou; Yichen Fan; Ya Li; Yekun Han; Qi’ao Yang; Lei Wang; Zhilong Peng; Shaohua Chen (Chemical Engineering Journal, 2026)

Depolymerization-dissolution of lignocellulose in room-temperature acid leaching treatment - Yichen Liu; Wenli Wang; Yue Wang; Longfei Liu; Guiying Li; Changwei Hu (Biomass and Bioenergy, 2026)

Monitoring of organochlorine pesticide residues in agricultural soils and associated risk assessment in central Jilin province, China - Jinying Li; Yanan Chen; Dianqi Pan; Jiquan Zhang; Yichen Zhang; Wanying Shi (Journal of Soils and Sediments, 2026)

System-Level Optimization of AUV Swarm Control and Perception: An Energy-Aware Federated Meta-Transfer Learning Framework with Digital Twin Validation - Zinan Nie; Hongjun Tian; Yijie Yin; Yuhan Zhou; Wei Li; Yang Xiong; Yichen Wang; Zitong Zhang; Yang Yang; Dongxiao Xie; Manlin Wang; Shijie Huang (Journal of Marine Science and Engineering, 2026)
Deep-sea exploration increasingly relies on Autonomous Underwater Vehicles (AUVs) to enable persistent, wide-area surveying in harsh and uncertain environments. In practice, however, deployments are constrained by tight energy budgets and bandwidth-limited, intermittent acoustic links, which complicate mission-level coordination. Moreover, many existing systems treat perception and control as loosely coupled modules, often resulting in redundant sensing, inefficient communication, and degraded overall performance—particularly under heterogeneous sensing modalities and shifting geological conditions. To address these challenges, we propose a hierarchical Federated Meta-Transfer Learning (FMTL) framework that tightly integrates collaborative perception with adaptive control for swarm optimization. The framework operates at three levels: (1) Representation Learning aligns heterogeneous sensors in a shared latent space via a physics-informed contrastive objective, substantially reducing communication overhead; (2) Meta-Learning Adaptation enables rapid transfer and convergence in new environments with minimal data exchange; and (3) Energy-Aware Control realizes closed-loop exploration by coupling Federated Explainable AI (FXAI) with decentralized multi-agent reinforcement learning (MARL) for path planning under energy constraints. Validated in high-fidelity hardware-in-the-loop simulations and a digital-twin environment, FMTL outperforms state-of-the-art baselines, achieving an AUC of 0.94 for target identification. Furthermore, an energy–intelligence Pareto analysis demonstrates a 4.5× improvement in information gain per Joule. Overall, this work provides a physically consistent and communication-efficient blueprint for the optimization and control of next-generation intelligent marine swarms.

Nonlinear Dynamics and Control of Tension Leg Platform Floating Wind Turbines: A Review - Jiawen Li; Lei Yan; Guibin Chen; Yichen Jiang; Mingfu Tang (Journal of Marine Science and Engineering, 2026)
As offshore wind power development advances into deeper waters, tension leg platform (TLP) floating wind turbines stand out for their excellent motion performance, lightweight structure design, and minimal seabed footprint. This paper reviews the advancements in TLP technology, covering structural configurations, dynamic characteristics and control strategies. Particular emphasis is given to analyzing dynamic response under combined environmental loads, including nonlinear motions induced by higher-order wave forces and parametric excitations, as well as the multiphysics coupling mechanisms involving aerodynamics, hydrodynamics, servo control, and structural dynamics. The review concludes by outlining future trends in platform scaling, intelligent operation and maintenance, and multi-energy integration. Overall, this review provides strategic insights for further research and engineering applications of TLP floating wind turbines.

Ribavirin acts as a candidate insect growth regulator: Providing sustainable control potential for Rhopalosiphum padi - Li Xu; Jingkun Li; Fei Miao; Zhiwen Zhao; Yichen Fu; Hengxu Yan; Sen Huang; Hao Yu; Runqiang Liu; Dongzhi Li (Crop Protection, 2026)

Resilience assessment of interdependent transit networks: an indifference perception threshold-based approach - Yichen Liang; Yajuan Deng; Chen Zhang; Ketong Hao; Yujie Guo; Yu Li; Liangbin Cui (Transportation Research Part D: Transport and Environment, 2026)

Smart textiles based on liquid crystal elastomers with photochromic and thermally actuated properties - Ye Zhang; Minghao Li; Xin Zhang; Wendi Wang; Yichen Yao; Guangwei Shao; Siyi Bi; Nanliang Chen; Jinhua Jiang; Huiqi Shao (Chemical Engineering Journal, 2026)

Vapor pretreatment-mediated crystal quality optimization for all-vacuum-processed monolithic perovskite/silicon tandem solar cells - Yichen Dou; Changyu Duan; Shenghan Hu; Xinyu Deng; Yuanyuan Chen; Anqi Kong; Yong Peng; Xiong Li; Zhiliang Ku (Chemical Engineering Journal, 2026)

Novel bio-based active packaging film with colloidosome-encapsulated clove essential oil - Yichen Yang; Li Yang; Haiming Cheng (Chemical Engineering Journal, 2026)

Facile synthesis of regenerated chitosan nanowhiskers with concentration-dependent self-assembly behavior - Ruicai Xia; Li Wang; Lei Chen; Xiaodi Liu; Yuqing Chang; Yichen Tian; Zhiping Jin; Qiang Zhang (Carbohydrate Polymers, 2026)

Nitrogen uptake strategies associated with phenological processes in a citrus orchard covered with smooth vetch - Xin Yang; Jiajia Zhang; Lei Lei; Qiuling Zhou; Yichen Li; Hongbing Yang; Lixiong Zeng; Wenfa Xiao (Plant and Soil, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

Targeted breeding of Litopenaeus vannamei for resistance to acute hepatopancreatic necrosis disease using the IRF-SSR molecular marker - Bin Yin; Yang Hu; Xuheng Yan; Yibin Chen; Yichen Hu; Sedong Li; Chaozheng Li; Jianguo He (Aquaculture, 2026)

Mediator subunit 16 positively modulates rice root development by associating with auxin response factor 10 - Yichen Mao; Luyao Wang; Jiyuan Li; Yixuan Fan; Peng Li; Chanjuan Mao (Plant Science, 2026)

From inhibition to enhancement: Time-staged complementary roles of sugarcane bagasse ash and red mud in sustainable cementitious composites - Chaofan Yi; Xingguo Ma; Yuheng Li; Qi Cui; Zheng Chen; Jianhui Liu; Yichen Wang (Journal of Cleaner Production, 2026)

Origin and diagenetic evolution of claystones in the CP2 coal seam, Adaohai Mine, Daqingshan Coalfield: Evidence from mineralogy and geochemistry - Ni He; Shangying Li; Hongfei Cheng; Zhenxiao Wu; Yichen Wang; Shaoxian Liang (International Journal of Coal Geology, 2026)

Polystyrene microplastics alter the toxicity of 6PPD to zebrafish (Danio rerio) larvae - Yuexing Zhao; Weitao Liu; Jianfeng Feng; Ning Gao; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Jianling Wang; Qi Wang; Chuan Yin; Xinwei Shi; Xiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A self-healing e-skin for quadruple-modal sensing - Henghui Wang; Hao Xue; Yapeng Song; Junjie Yuan; Huijun Cao; Quan Yuan; Yichen Zhu; Jonghwan Suhr; Jintang Li; Siwei Li; Yingjie Guo; Liyun Li; et al. (Chemical Engineering Journal, 2026)

An empirical study on the compound effects of extreme weather and UHI on building energy consumption under urban local climate - Shuyang Zhang; Nianxiong Liu; Xiyu Wu; Yichen Han; Wenwen Li; Fang Guo; Xiujiao Song; Chao Yuan (Building and Environment, 2026)

Rhizosphere microbiota mediated by sulfur fertilizer regulates flavor quality in peppers (Capsicum annuum L.) - Huan Zhang; Yutong Chi; Yichen Xin; Chunmiao Fang; Ming Li; Yao Lv (Protoplasma, 2026)

DeSUMOylation of Spastin Enhances AMPA Receptor Recycling and Synaptic Plasticity via IST1-Dependent Endosomal Sorting - Jiong Li; Bingyu Ren; Yichen Yin; Kedong Chen; Meiying Chen; Guangyin Yu; Guoqing Guo; Jifeng Zhang; Caihui Cha; Laijian Wang (Molecular Neurobiology, 2026)

Comprehensive quality evaluation and principal component analysis of Crassostrea gigas from North Yellow Sea, China: characterizing nutritional, flavor, and functional profiles - Shanqin Huo; Jixing Peng; Xinnan Zhao; Yichen Lin; Xudong Li; Zhijun Tan (Journal of Oceanology and Limnology, 2026)

A meta-heuristic assisted path planning method for unmanned underwater vehicles and experimental validation - Jinsi Cai; Haiyan Xiao; Yichen Li; Guanghua Li; Dongdong Hou; Bingju Lu (Ocean Engineering, 2025)

Earthworm intestine orchestrates dual host-microbiome detoxification of 6PPD-quinone - Ruiying Shi; Weitao Liu; Xinwei Shi; Xiang Li; Yichen Ge; Jinzheng Liu; Aurang Zeb; Yuexing Zhao; Yuebing Sun; Jing An (Journal of Hazardous Materials, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Tunable-performance sustainable bamboo composites via thinning and bioinspired layered reassembly - Xianke Wang; Yichen Yang; Xiaohan Chen; JianChang Lian; Yuquan Li; Huanrong Liu; Xinxin Ma; Changhua Fang (Journal of Cleaner Production, 2025)

Nano–lignocellulose powder by hydrolysis–oxidation synergism for high strength and adequate barrier bio-composites - Zhikang Su; Yichen Liu; Bing Jiang; Chaohui Yang; Benyou Liu; Maocheng Ji; Yanhui Li; Chuanwei Zhang (Journal of Cleaner Production, 2025)

Foliar exposure to 6PPD-Q disturbs photosynthetic processes and induces oxidative stress in Eichhornia crassipes - Yichen Ge; Ruiying Shi; Weitao Liu; Xiang Li; Xinwei Shi; Aurang Zeb; Yuexing Zhao; Jing An; Yuebing Sun (Journal of Environmental Management, 2025)

Harmonizing satellite and ground NO2 observations in China: A multi-sensor framework for scenario-specific calibration - Jianbin Gu; Xiaoxia Liang; Shipeng Song; YiChen Li; Liangfu Chen; Jinhua Tao; Yanfang Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Analysis on the difference of nutrient components of black wolfberry seed grown in different regions - Yichen Liu; Wenyuan Zhang; Yanjun Li; Ruhui Shen; Shuaibei Wang; Xue Wang; Jianjun Deng; Zhenzhen Xu; Haixia Yang (Food Research International, 2025)

Biomimetic confined synthesis of copper-enriched polydopamine single-atom catalyst for synergistic catalysis of ammonium perchlorate and ammonium dinitramide decomposition - Wenqi Zhu; Chong Chen; Hongfeng Ji; Yong Kou; Yanchen Wang; Yichen Li; Qiangqiang Lu; Jun Di; Guigao Liu; Wei Jiang; Lei Xiao; Gazi Hao (Chemical Engineering Journal, 2025)

Analytical Solution for Dynamic Responses of Distinct Tubular Piles Under Vertical Seismic Excitation Considering Water–Pile–Soil Interaction - Yiming Huang; Jiaxi Zhou; Xin Li; Yichen Liu; Piguang Wang (Journal of Marine Science and Engineering, 2025)
Offshore tubular pile systems in earthquake-active marine regions face risks from vertical seismic excitation, water dynamics, and pile–soil interactions. Thus, an analytical solution for offshore tubular piles considering multi-physical field coupling (the mutual interactions between seawater, tubular pile, and surrounding soil) is developed to investigate their dynamic responses under vertical seismic loading. Firstly, the dynamic response of the tubular pile system is decomposed into free-field and scattered-field components. The governing equations for water, soil, and tubular piles (one-dimensional and three-dimensional tubular pile models) are established, with the strict enforcement of boundary conditions such as displacement continuity and stress equilibrium. Then, analytical solutions for both one-dimensional and three-dimensional tubular pile models are derived. The proposed framework is validated by comparison with existing literature solutions, confirming its rationality. Subsequently, parametric analyses are conducted to explore the influences of key factors. The results indicate that it is essential to consider the coupled effects of vertical earthquakes and water–pile–soil interaction in the design of offshore tubular piles, as neglecting multi-field coupling or adopting oversimplified models can lead to inaccurate predictions of dynamic responses.

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

Triple-platform validation of TROPOMI v2.4 NO2 retrievals: Quantifying surface albedo-driven changes across monsoon-vegetation regimes - Jianbin Gu; Jinhua Tao; Meng Fan; Mingge Li; Yawen Kong; Yichen Li; Liangfu Chen (Environmental Research, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Comprehensive analysis of prevailing weather patterns and high-impact typhoon tracks to reveal where and how tropical cyclone affects regional ozone pollution in the Yangtze River Delta region, China - Mengzhu Xi; Yi Luo; Yichen Li; Danyang Ma; Lingyun Feng; Shuxian Zhang; Shitong Chen; Min Xie (Atmospheric Environment, 2025)

Phosphorylation of a conserved TBXT threonine residue is vital to vertebral development - Shuxia Chen; Chennan Liu; Ying Zhao; Lingbo Wang; Rui Peng; Lei Lu; Qian Yu; Yichen Jin; Jinsong Li; Xueyan Yang; Yunping Lei; Hongyan Wang (Science China Life Sciences, 2025)

Cellular optical imaging techniques: a dynamic advancing frontier - Yaning Li; Chuankang Li; Caiwei Zhou; Jie Wang; Weixing Li; Tianying Pan; Chenying He; Xiaodong Guan; Yichen Wang; Yingda Huang; Xianao Zhao; Lusheng Gu; et al. (Science China Life Sciences, 2025)

Differential response of runoff-sediment hysteresis relationships to watersheds hydrological structural connectivity - Taoxi Li; Ming Lei; Gang Sun; Qian Zeng; Yu Long; Yichun Ma; Yichen Yin; Peiyao Xiao; Jiale Ye; Zhongwu Li; Yaojun Liu (Journal of Hydrology, 2025)

Precise Li+ and Mg2+ separation enabled by sodalite ion exchange contribute to the lithium extraction from low-quality brines - Jiayi Wang; Yichen Hao; Jinping Li; Jiangfeng Yang (Journal of Hazardous Materials, 2025)

Preparation high-efficiency NH2-MIL-125@g-C3N4 NADH photo-regeneration catalyst for enzymatic conversion of furfural to furfural alcohol - Shuaizhe Li; Xingyong Li; Senshen Yu; Qingtao Wang; Na Liu; Yichen Nie; Xuexiang Fu; Mengke Dong; Haolin Li; Yanliang Guo; Phidsavard Keomeesay; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Walnut xylem-derived activated carbon with microtubule bundle architectures for highly efficient and rapid treatment of methylene blue - Shuang Jia; Zhijie Mao; Bo Zhang; Yaru Wang; Tianyang Sun; Guanhua Jin; Chuang Wang; Yichen Lv; Shouzhu Li; Dan Sun (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

Cobalt-based nano-MOF additive to aluminum for enhancing energy release of energetic components - Chong Chen; Wenqi Zhu; Yanchen Wang; Jin Zhu; Qiangqiang Lu; Yichen Li; Lei Xiao; Jun Di; Guigao Liu; Wei Jiang; Gazi Hao (Chemical Engineering Journal, 2025)

A bispecific nanoregulator for T cell targeting-mediated sequential immunotherapy with spatiotemporal orchestration of tumor microenvironment - Weijing Yang; Kaixin Zhang; Yichen Guo; Xiao Weng; Yayun Wang; Xinxin Wang; Guodong Zhao; Yongjuan Li; Lei Wang (Chemical Engineering Journal, 2025)

Finite element modeling of the biomechanical properties of Populus tomentosa branches and analysis of pruning mechanisms - Yichen Ban; Yang Liu; Shihong Ba; Kun Lyu; Jian Wen; Xiaopeng Bai; Wenbin Li (Computers and Electronics in Agriculture, 2025)

High-frequency sequence patterns in lacustrine basins: Insights from delta-hyperpycnal flow systems in the Middle Jurassic shale interval, Sichuan Basin, China - Haocheng Shi; Benzhong Xian; Yichen Liu; Zhiyun Yu; Lin Zhao; Junyang Geng; Rongheng Tian; Qianran Wu; Li Liu; Yujie Shuai; Yi Shu (Sedimentary Geology, 2025)

Metabolomic alterations reveal toxic mechanisms of single and combined 6PPD and arsenic exposure on mung bean (Vigna radiata) - Sheharyar Khan; Aurang Zeb; Weitao Liu; Hamra Tariq; Abdul Mateen Baig; Hifza Iqbal; Ruiying Shi; Jinzheng Liu; Yuexing Zhao; Xiang Li; Yichen Ge (Journal of Hazardous Materials, 2025)

Ribavirin showed insect growth regulator activity to Helicoverpa armigera - Li Xu; Yin Huang; Zezheng Liu; Qi Zuo; Minghui Long; Yichen Fu; Runqiang Liu; Yunchao Kan; Dongzhi Li (Journal of Asia-Pacific Entomology, 2025)

A grazing pressure mapping method for large-scale, complex surface scenarios: integrating deep learning and spatio-temporal characteristic of remote sensing - Yingqi Wang; Huiping Huang; Yichen Tian; Guang Yang; Liping Li; Chao Yuan; Fan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Mechanisms of aristolochic acid I Hepatotoxicity: Central role of PDK4-Induced mitochondrial dysfunction and hepatic inflammation - Zhaobin Wang; Kunyang Li; Xiaoqi Yi; Yichen Wu; Yang Zhao; Pingping He; Qinghua Zeng; Enxiang Zhang (Food and Chemical Toxicology, 2025)

Modeling the Formation and Propagation of Equidistant Fractures in Layered Rock Masses Using the Advanced Peridynamic Method - Pengfei Ma; Yichen Zhang; Yuancheng Li; Lichao Nie; Chao Yuan (Rock Mechanics and Rock Engineering, 2025)

Genetic Correlations and Causalities between Alzheimer’s Disease and 35 Biomarkers in Blood and Urine - Sheng Zhang; Yu-Lin Yao; Yichen Li; Xiaofan Zhang; Yong Wu (Molecular Neurobiology, 2025)

D* Lite and Transformer-Enhanced SAC: A Hybrid Reinforcement Learning Framework for COLREGs-Compliant Autonomous Navigation in Dynamic Maritime Environments - Tianqing Chen; Yamei Lan; Yichen Li; Jiesen Zhang; Yijie Yin (Journal of Marine Science and Engineering, 2025)
Autonomous navigation in dynamic, multi-vessel maritime environments presents a formidable challenge, demanding strict adherence to the International Regulations for Preventing Collisions at Sea (COLREGs). Conventional approaches often struggle with the dual imperatives of global path optimality and local reactive safety, and they frequently rely on simplistic state representations that fail to capture complex spatio-temporal interactions among vessels. We introduce a novel hybrid reinforcement learning framework, D* Lite + Transformer-Enhanced Soft Actor-Critic (TE-SAC), to overcome these limitations. This hierarchical framework synergizes the strengths of global and local planning. An enhanced D* Lite algorithm generates efficient, long-horizon reference paths at the global level. At the local level, the TE-SAC agent performs COLREGs-compliant tactical maneuvering. The core innovation resides in TE-SAC’s synergistic state encoder, which uniquely combines a Graph Neural Network (GNN) to model the instantaneous spatial topology of vessel encounters with a Transformer encoder to capture long-range temporal dependencies and infer vessel intent. Comprehensive simulations demonstrate the framework’s superior performance, validating the strengths of both planning layers. At the local level, our TE-SAC agent exhibits remarkable tactical intelligence, achieving an exceptional 98.7% COLREGs compliance rate and reducing energy consumption by 15–20% through smoother, more decisive maneuvers. This high-quality local control, guided by the efficient global paths from the enhanced D* Lite algorithm, culminates in a 10–32 percentage point improvement in overall task success rates compared to state-of-the-art baselines. This work presents a robust, verifiable, and efficient framework. By demonstrating superior performance and compliance with rules in high-fidelity simulations, it lays a crucial foundation for advancing the practical application of intelligent autonomous navigation systems.

Potential of carbon emissions from heating in hot summer and cold winter urban residential areas in China through 2050 - Yuqiu Liu; Zhengnan Zhou; Yichen Han; Chaohong Wang; Wenwen Li; Yingyu Chen; Yingkai Lian; Haoran Chen (Energy and Buildings, 2025)

Spatiotemporal warning of rainfall-induced railway geohazards in China - Bohao Li; Kai Liu; Ming Wang; Weihua Zhu; Ziyu Jiang; Ningning Qiao; Yichen Yan; Junfei Liu; Jing Zhao; Chenxia Li (Engineering Geology, 2025)

Enlarged Perivascular Spaces (EPVS) Associated with Functional and Cognitive Outcome After Aneurysm Subarachnoid Hemorrhage (aSAH) - Haichao Wang; Qiuyue Yu; Wenyi Zhang; Shengqi Yao; Yun Zhang; Qiong Dong; Yichen Zhao; Jinxing Lin; Xueyuan Liu; Li Gong (Translational Stroke Research, 2025)

Identification of STAT3 phosphorylation inhibitors using generative deep learning, virtual screening, molecular dynamics simulations, and biological evaluation for non-small cell lung cancer therapy - Weiji Cai; Beier Jiang; Yichen Yin; Lei Ma; Tao Li; Jing Chen (Molecular Diversity, 2025)

Transfer of peripersonal space to a virtual body in young adults and exploration of adult age differences - Dariusz O’Leary; Yichen Fan; Ina Schattenberg; Andrea Serino; Shu-Chen Li (Experimental Brain Research, 2025)
Peripersonal space (PPS) is known as the representation of the area around the body. Past research has shown that inducing a full-body illusion (FBI) can lead to PPS extending at the physical body location. However, it is unclear whether such illusions may also result in PPS transferring to a virtual body that is separate from the physical body. Furthermore, whether this effect may change over the course of natural aging is currently unknown. In three experiments, we investigated whether inducing an FBI using an avatar presented from a third-person perspective in virtual reality, results in PPS transferring to the avatar, and whether this effect differs between young (YAs; 18–29 years) and older adults (OAs; 65–83 years). We utilized a manipulation involving either synchronous or asynchronous stroking for FBI induction and assessed ratings of avatar ownership as a subjective indicator of embodiment. Meanwhile effects on PPS were measured by differences in multisensory facilitation within a visuo-tactile task. While we found significantly stronger ownership ratings for synchronous compared to asynchronous stroking in both YAs and OAs, this difference, as well as the degree of ownership, was significantly weaker for OAs. Moreover, while a distance-dependent modulation of multisensory facilitation reflecting PPS at the avatar’s location was observed in two samples of YAs, this effect was absent in OAs. These findings suggest that PPS in YAs can transfer to an avatar in virtual reality, while age-related differences in susceptibility to the FBI might contribute to a lack of this effect in OAs.

Exploring heterogeneity in evacuation decision of urban residents between utility and regret decision rules under a flood hazard - Zeqian Jin; Yichen Wang; Chen Li; Chengcheng Yu; Xin Ye; Jiantao Mu (Sustainable Cities and Society, 2025)

Incorporation of disulfide bonds into ionizable lipids enables efficient splenic mRNA delivery and potent immunotherapy in mice - Yichen Li; Yi Cao; Hao Bai; Luwei Zhang; Baiqiu Chen; Chengfan Wu; Qi Shuai; Yunfeng Yan (Chemical Engineering Journal, 2025)

A study of the neurophysiological effects of peppermint odor on human thermal comfort - Songtao Hu; Yang Yang; Mingli Lu; Yichen Liu; Silin Zheng; Hongyu Guan; Li Tong (Building and Environment, 2025)

Melatonin integrates multiple biological and phytohormonal pathways to enhance drought tolerance in rice - Chanjuan Mao; Luyao Wang; Yichen Mao; Yingyin Li; Yizhi Peng; Yixuan Fan; Jiyuan Li; Yu Zhu; Xiaofeng Xu; Peng Li (Planta, 2025)

Impact of residential morphology on outdoor thermal comfort and building energy consumption in winter and summer: A case study - Minghao Wang; Yichen Dong; Wei Liao; Bo Pan; Sensheng Li; Junchao Duan; Shen Xu (Urban Climate, 2025)

The Effect of the Belt and Road Initiative (BRI) on Non-CO2 Agricultural Greenhouse Gas Emission Trends in Southeast Asian Countries - Minpeng Chen; Siqi Li; Xun Su; Yichen Feng; Yichun Peng (Resources, Conservation and Recycling, 2025)

Temperature-controllable antibacterial film mediated by a photoresponsive metal-polyphenol framework for long-term food preservation - Guangyang Jiang; Wenyang Sheng; Li Yang; Yichen Yang; Tingting Tang; Chenzhi Wang; Yongqiang Tian (Food Control, 2025)

Magmatic dikes in the Chang'e-6 sampling area - Qingyun Deng; Zhiyong Xiao; Yunhua Wu; Pei Ma; Wei Cao; Yichen Wang; Yizhen Ma; Fanglu Luo; Fei Li (Earth and Planetary Science Letters, 2025)

Amino functionalization of covalent organic frameworks for enhancing adsorption capacity of radioactive iodine - Yichen Li; Jie Zhang; Xinxin Wang; Ruixue Meng; Yinxiao Zhang; Lianwei Yin; Xinxin Pi; Qiuju Du; Long Chen; Yanhui Li (Chemical Engineering Journal, 2025)

CsHFDF bifunctional polar molecule-assisted synergistic passivation for highly efficient and stable perovskite solar cells - Jiahao Cheng; Jiawei Song; Meiyin Li; Wenjian Shen; Yichen Yang; Xin Zhang; Liu Liu; Jianlin Xu; Guijie Liang; Bin Li; Yong Peng; Peng Zhou; et al. (Chemical Engineering Journal, 2025)

Continuous organic mulching enhances the stability of soil organic carbon in Phyllostachys praecox: A 5-year in situ experiment - Yichen Zhang; Xiaomin Ge; Qiang Li; Shunyao Zhuang; Minmei Shi; Xingzhao Huang; Zhuangzhuang Qian (Soil Ecology Letters, 2025)

Impact of meridional wave-induced transport on sea surface temperature in mid -low latitude cold tongues - Yichen Wang; Kejian Wu; Rui Li; Wenqing Zhang; Xianghui Dong; Lingyun Lyu (Frontiers in Marine Science, 2025)
This study employs reanalysis data published by ECMWF to investigate the impact of ocean waves on cold tongues in the southern hemisphere. Based on the global sea surface temperature (SST) patterns, the scope of the cold tongue is defined in this paper. Compared to Ekman transport, wave transport dominates and plays a critical role in the cold tongue region. This study analyzes the characteristics of cold tongues across the three major ocean, with a primary focus on the Pacific cold tongue, which serves as the most representative region. Analysis of the relationship between meridional wave transport and SST in the southeastern Pacific cold tongue indicates a lagged negative correlation between abnormal SST and meridional wave-induced water transport from high latitudes. Specifically, negative SST anomalies in the Pacific cold tongue occur 3~4 months after a positive anomaly in northward cold-water transport from high latitudes. Meridional wave transport between 30°S and 38°S has a significant cooling effect on SST in the cold tongue region, with the strongest cooling observed along the northeastern coastline. Additionally, the combined effects of northward and westward water transport result in a distinct temperature gradient in the western cold tongue. These findings highlight the connection between wave-induced transport and the cold tongue, providing a novel perspective for exploring the causes of SST anomalies.

How do FDI and tax competition of local governments affect PM2.5 rebound effects? Evidence from China - Xiao Han; Yi Li; Meiying Xie; Yichen Wang (Journal of Environmental Management, 2025)

Bacterial cellulose and photothermal material from biomass-based zero-waste biorefinery functionalized chitosan film for sustainable active food packaging - Li Yang; Wenyang Sheng; Yichen Yang; Ying Yang; Kaiwen He; Guangyang Jiang; Yongqiang Tian (Food Hydrocolloids, 2025)

Metagenomics reveals an increased proportion of an Escherichia coli-dominated enterotype in elderly Chinese people - Jinyou Li; Yue Wu; Yichen Yang; Lufang Chen; Caihong He; Shixian Zhou; Shunmei Huang; Xia Zhang; Yuming Wang; Qifeng Gui; Haifeng Lu; Qin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Photothermally inducing SnS2 phase transition in Cu2O@CuS@SnS2 core–shell heterostructure to trigger efficient photocatalytic CO2 reduction - Yaqi Liu; Yichen Liu; Guicheng Luo; Wentao Zhu; Ning Li; Yi Song; Huaju Song; Yun Shan; Qifan Wu; Yanan Ding; Aiping Liang; Lizhe Liu (Chemical Engineering Journal, 2025)

Statistical and theoretical analysis of iodine spiking phenomena during steam generator tube rupture - Changdong Lu; Yichen Chen; Zhijun Li; Pingting Jiang; Chao Yu; Pengtao Fu (Annals of Nuclear Energy, 2025)

Enhanced bio-reduction of Cr(VI) using Shewanella putrefaciens CN32 mediated by Fe(III) minerals and riboflavin synergistically - Tianle Zhang; Haibo Li; Yichen Wu; Yajue Yuan; Yu Du (Biodegradation, 2025)

Reconstruction of 2‐m Air Temperature From ERA5 Reanalysis at Dome A, Antarctica - Yifan Wu; Yu Jiang; Yi Zhang; Yichen Li; Xin Chen; Wenqian Zhang; Xi Zhao (International Journal of Climatology, 2025)
In this study, we jointly used in situ air temperature from AWS and reanalysis data from ERA5 to make the first‐ever reconstruction of a 42‐year (1978–2020) air temperature time series for Dome A, Antarctica. By analysing the impact of environmental variables, we found that the 10‐m u‐component of wind was the predominant one for air temperature bias between ERA5 and AWS, followed by total cloud cover. Air temperature deviations between ERA5 and AWS during the period of 2005–2020 were successfully reduced by applying a random forest (RF) model, decreasing the bias by 0.52°C, the RMSE by 3.16°C and the MAE by 2.77°C. We next applied the RF model to predict the 2‐m air temperature difference which was added back to correct ERA5 from 1978 to 2004. This yielded an accurate time series of air temperature from 1978 to 2020. Using the innovative trend analysis method to analyse the temperature trend of the corrected data, we found that Dome A has experienced a gradual warming of 0.10°C dec −1 over the 42‐year period. Among the seasonal temperature changes, spring showed a significant warming trend of 0.57°C dec −1 , autumn and winter showed no significant warming, while summer showed a slightly cooling trend. Also, over the 42‐year analysis period, a stable oscillation period of ~28 year was observed. This cycle emerged as the dominant pattern, influencing the overall temperature evolution. The method proposed in this research, which combines machine learning with AWS to correct ERA5 air temperature data, holds the potential to address spurious changes of reanalysis data in long‐time series studies, thus improving the reliability of trend analyses.

Reservoir operation considering carbon benefits of drawdown zone emissions - Yichen Yang; Pan Liu; Shiqiong Li; Yibo Wang; Yang Liu (Journal of Hydrology, 2025)

Respiration-Driven Ammonia Sensing Mask for Multifunctional Self-powered Monitoring Application - Jinzhu Huang; Yichen Huang; Ting Li; Haoming Xu; Hanguang Wu; Zhiqiang Su (Chemical Engineering Journal, 2025)

Cellulose nanofiber-created air barrier enabling closed-cell foams prepared via oven-drying - Li Wang; Yichen Tian; Yuqing Chang; Lei Chen; Qiang Zhang (Carbohydrate Polymers, 2025)

How gender difference affects children's outdoor thermal physio-psychological responses? A comparative field study - Yichen Li; Yang Li; Guanning Shang; Zijing Peng; Xinyue Zhang; Bo Hong (Building and Environment, 2025)

Identification of Key Genes and Immune Characteristics of SASP in Acute Ischemic Stroke - Hanlu Cai; Huixue Zhang; Guanghao Xin; Shanshan Peng; Fanfan Xu; Nan Zhang; Yichen Li; Wei Zhang; Ying Li; Yingjie Ren; Yu Wang; Zhaojun Liu; et al. (Journal of Molecular Neuroscience, 2025)

Use of the diffusive gradients in thin-films (DGT) technique for smart rapid biomonitoring of trace metals in aquaculture systems - Runmei Wang; Jian Lu; Jun Wu; Yichen Lin; Feng Li; Cui Zhang; Jianhua Wang; Yingmin Zhou; Xiupeng Yue (Marine Environmental Research, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Photo-responsive Cu-tannic acid nanoparticle-mediated antibacterial film for efficient preservation of strawberries - Wenyang Sheng; Li Yang; Yichen Yang; Chenzhi Wang; Guangyang Jiang; Yongqiang Tian (Food Chemistry, 2025)

Camellia seed oil exerts a more gradual influence on the progression of high-fat diet induced NAFLD mice compared to corn oil: Insights from gut microbiota and metabolomics - Yuan Zhou; Zichuan Wang; Jianbiao Li; Junjie Qiu; Yichen Wang; Huihui Tao; Chengyu Shentu; Yingjie Luo; Jiahui Zhao; Tengfei Xu (Food Bioscience, 2025)

Air pollution exposure disparities across age groups in Beijing-Tianjin-Hebei region from 2010 to 2020 - Lili Wang; Yichen Wang; Quanbao Jiang; Junji Cao; Zhanfeng Dong; Shuzhuo Li (Environmental Pollution, 2025)

Zero-carbon renewal of communities through collaborative retrofitting of multi-scale design elements: A case of Wuhan, China - Shen Xu; Huangwanjin Zhou; Yichen Dong; Qiuguo He; Gaomei Li (Energy and Buildings, 2025)

A trackable mitochondria-targeting nanosystem for mitochondrial redox and mitophagy regulation in diabetic retinopathy management - Yangxue Yao; Xiaoyu Lei; Xun Li; Yichen Ge; Yun Wang; Xin Qin; Yang Gao; Geru Zhang; Yunfeng Lin; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Pedigree reconstruction based on target sequencing in Pacific white shrimp Litopenaeus vannamei - Junqing Yang; Yang Yu; Yizhou Zhou; Zhenning Bao; Yichen Liu; Jinsheng Sun; Fuhua Li (Aquaculture, 2025)

Fabrication of the ferritin-mannoprotein shell-core heteroprotein complex for stabilization of bioactive molecules - Xinmei Sha; Runxuan Chen; Yichen Li; Tianyang Wang; Ku Li; Hui Guo; Yuyu Zhang; Rui Yang (Food Hydrocolloids, 2025)

Regenerated carboxymethyl cellulose beads for selective removal of low-density lipoprotein from whole blood - Yichen Tian; Yuele Kong; Xiaodi Liu; Lei Chen; Li Wang; Lin Zhou; Guodong Wang; Qiang Zhang (Carbohydrate Polymers, 2025)

Independent Tri-Spectral Integration for Intelligent Ship Monitoring in Ports: Bridging Optical, Infrared, and Satellite Insights - Yichen Feng; Hui Yin; Hao Zhang; Langtao Wu; Haihui Dong; Jiawen Li (Journal of Marine Science and Engineering, 2024)
Image-based ship monitoring technology has extensive applications, and is widely used in various aspects of port management, including illegal activity surveillance, vessel identification at entry and exit points, channel and berth management, unmanned vessel control, and incident warning and emergency response. However, most current ship identification technologies rely on a single information source, reducing detection accuracy in the complex and variable marine environment. To address this issue, this paper proposes a knowledge transfer-based ship identification system integrating three modules. The system enables synchronized monitoring of visible light coastal images, satellite cloud images, and infrared spectrum images, thereby mitigating problems such as low detection accuracy and poor adaptability of image recognition. Additionally, extensive supplementary experiments were conducted to evaluate the effectiveness of the preprocessing and data augmentation modules as well as the transfer learning module. The study also discusses the limitations of current deep learning-based ship monitoring models, particularly their poor adaptability to image recognition and inability to achieve all-weather, round-the-clock monitoring. Experimental results based on three ship monitoring datasets demonstrate that the proposed system, by integrating three distinct detection conditions, outperforms other models with an F1-score of 98.74%, approximately 10% higher than most existing ship detection systems.

Phytotoxicity of 6PPD and its uptake by Myriophyllum verticillatum: Oxidative stress and metabolic processes - Yuexing Zhao; Weitao Liu; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Xiang Li; Yichen Ge (Science of The Total Environment, 2024)

Response of Ceratophyllum demersum L. and its epiphytic biofilms to 6PPD and 6PPD-Q exposure: Based on metabolomics and microbial community analysis - Xiang Li; Weitao Liu; Yichen Ge; Ruiying Shi; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Qi Wang; Jianling Wang; Fan Mo; Aurang Zeb; Miao Yu (Journal of Hazardous Materials, 2024)

Evanescent hormesis effect induced by environmentally relevant PFOS to marine Chlorella sp. - Xiaofeng Li; Zhiguang Niu; Meiqi Jing; Yongzheng Ma; Ying Zhang; Yichen Yang (Journal of Hazardous Materials, 2024)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

The behavior and model of methane adsorption on coal by ultrasonic enhancement - Shidong Cui; Qingmin Shi; Yong Qin; Ruijun Ji; Chunhao Li; Yichen Mi; Ben Zhao (Fuel, 2024)

MAPK signaling pathway enhances tolerance of Mytilus galloprovincialis to co-exposure of sulfamethoxazole and polyethylene microplastics - Yanan Di; Liya Li; Jianzhou Xu; Ao Liu; Ruoxuan Zhao; Shuimei Li; Yichen Li; Jiawei Ding; Siyu Chen; Mengjie Qu (Environmental Pollution, 2024)

Effects of dynamic airflows on convective cooling of human bodies − Advances in thermal comfort assessment and engineering design - Jianong Li; Siqi Zhou; Yichen Yu; Jianlei Niu (Energy and Buildings, 2024)

The breaching mechanism of moraine dams with buried ice: A Review - Yunying Mou; Huayong Chen; Tao Wang; Hechun Ruan; Xiao Li; Yunhan Yu; Yichen Zhou; Haoyang Meng (Cold Regions Science and Technology, 2024)

Recent advances on transport and transformation mechanism of nanoplastics in lung cells - Simeng Zhang; Hangxi Zhang; Yichen Li; Zhiwei Sun; Yueyue Chen (Science of The Total Environment, 2024)

Environmental concentrations of 6PPD and 6PPD-Q cause oxidative damage and alter metabolism in Eichhornia crassipes - Yichen Ge; Jinzheng Liu; Ruiying Shi; Xiang Li; Aurang Zeb; Qi Wang; Jianling Wang; Yuexing Zhao; Miao Yu; Chuan Yin; Hongxia Xiong; Weitao Liu (Science of The Total Environment, 2024)

Comparative toxic effect of tire wear particle-derived compounds 6PPD and 6PPD-quinone to Chlorella vulgaris - Jinzheng Liu; Miao Yu; Ruiying Shi; Yichen Ge; Jiantao Li; Aurang Zeb; Zhipeng Cheng; Weitao Liu (Science of The Total Environment, 2024)

Study on the mooring systems attaching clump weights and heavy chains for improving the typhoon resistance of floating offshore wind turbines - Jiawen Li; Hongli Zuo; Jingjing Zuo; Yichen Jiang; Shi Liu (Ocean Engineering, 2024)

Spatial distribution and priority conservation areas identification in Three-River-Source National Park considering the multifaceted values of plants - Yingqi Wang; Huiping Huang; Liping Li; Yichen Tian; Chao Yuan (Journal of Environmental Management, 2024)

Comparison analysis of bioactive metabolites in soybean, pea, mung bean, and common beans: reveal the potential variations of their antioxidant property - Wenyuan Zhang; Yaqi Zhao; Haixia Yang; Yichen Liu; Yanli Zhang; Zhanquan Zhang; Yunlong Li; Xue Wang; Zhenzhen Xu; Jianjun Deng (Food Chemistry, 2024)

Machine vision-assisted genomic prediction and genome-wide association of spleen-related traits in large yellow croaker infected with visceral white-nodules disease - Yulin Bai; Miaosheng Feng; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Zhou Jiang; Pengxin Jiang; Sijing Chen; Longyu Chen; Wei Liu; Tingsen Jiang; Yichen Li; et al. (Fish & Shellfish Immunology, 2024)

A novel strategy for sequential separation of Th(IV) from highly acidic wastewater based on solid phase extraction - Yaowen Zhang; Yichen Hu; Juan Tong; Kesheng Hu; Binliang Li; Beijia Chang; Keliang Shi; Junqiang Yang; Xiaolin Hou (Chemical Engineering Journal, 2024)

Multi-Objective Optimization Design of a Mooring System Based on the Surrogate Model - Xiangji Ye; Peizi Zheng; Dongsheng Qiao; Xin Zhao; Yichen Zhou; Li Wang (Journal of Marine Science and Engineering, 2024)
As the development of floating offshore wind turbines (FOWTs) progresses from offshore to deeper sea, the demands on mooring systems to ensure the safety of the structure have become increasingly stringent, leading to a concomitant rise in costs. A parameter optimization method for the mooring system of FOWTs is proposed, with the mooring line length and anchor radial spacing as the optimization variables, and the minimization of surge, yaw, and nacelle acceleration as the objectives. A series of mooring system configuration samples are generated by the fully analytical factorial design method, and the open source program OpenFAST is employed to simulate the global responses in the time domain. To enhance the efficiency of the optimization process, a multi-objective evolutionary algorithm, Non-dominated Sorting Genetic Algorithm II (NSGA-II), is utilized to find the Pareto-optimal solutions, alongside a Kriging model, which serves as a surrogate model for the FOWTs. This approach was applied to an IEC 15MW FOWT to demonstrate the optimization procedure. The results indicate that the integration of the genetic algorithm and the surrogate model achieved rapid convergence and high accuracy. Through this optimization process, the longitudinal motion response of FOWTs is reduced by a maximum of 6.46%, the yaw motion by 2.87%, and the nacelle acceleration by 11.55%.

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Flexible and air-stable n-type oleylamine/carbon nanotube hybrid yarns for high-performance wearable thermoelectric generators - Fei Yin; Xiaogang Luo; Xuejiao Wang; Yunxia Liang; Tong Wu; Yichen Li; Ke-Qin Zhang (Chemical Engineering Journal, 2024)

Spatio-temporally controlled all-in-one hydrogel microspheres for ulcerative colitis treatment based on cocktail strategy - Xiao Wang; Weijian Cheng; Xuebo Li; Di Wang; Lijun Su; Yanfen Cheng; Yichen Hu; Chen Zhang; Jinming Zhang (Chemical Engineering Journal, 2024)

A novel piezoelectric fenton-like process mediated by FeOCl for efficient contaminant removal - Yichen Ding; Hao Tao; Zeyu Guan; Fan Yang; Dongya Li (Chemical Engineering Journal, 2024)

Dynamic Change Characteristics of Wetlands in Hefei and their Driving Factors Along the Urban–Rural Gradient - Hui Zhang; Chuntao Li; Yichen Zhang; Lang Zhang (Wetlands, 2024)
Wetlands, as vital components of urban ecological infrastructure, provide essential ecosystem services. However, they face increasing risks of degradation and loss due to their vulnerability, environmental changes, and human activities. Therefore, effective restoration efforts are urgently needed. This study adopts a novel approach by considering the urban–rural gradient and integrates land use data, ecological parameters, and anthropogenic factors in Hefei City. Through morphological spatial pattern analysis, principal component analysis, and affinity propagation, this study identifies and analyzes urban–rural gradients. Using the optimal parameter geographic detector, the drivers of wetland changes from 1990 to 2020 are quantitatively assessed across different urban–rural gradients in Hefei. The findings indicate the following. (1) A persistent reduction in wetland expanse throughout the study duration, diminishing from 1274.56 km 2 in 1990 to 1119.37 km 2 in 2020, constituting a decrement of 12.17%. (2) Based on geographic detector outcomes, disparate driving forces underpin wetland dynamics across urban–rural gradients, with urban locales predominantly influenced by organic carbon and the proportion of impervious surface factors. Meanwhile, in agricultural and semi-ecological villages, silt is the primary factor, while ecological villages are primarily modulated by both silt and gross domestic product factors. Additionally, synergistic interactions manifest heightened explanatory power. This study elucidates the mechanistic underpinnings of wetland dynamics along urban–rural gradients, providing pivotal insights for developing targeted wetland restoration and conservation policies pertinent to the urban–rural developmental trajectory in Hefei City. Concurrently, it offers relevant recommendations for the multifaceted stewardship and sustainable development of wetlands in Hefei City in the foreseeable future.

Effects of active vitamin D analogs and calcimimetic agents on PTH and bone mineral biomarkers in hemodialysis patients with SHPT: a network meta-analysis - Xing Liu; Yichen Liu; Peimin Zheng; Xun Xie; Zhouzhou Li; Rui Yang; Lie Jin; Ziwei Mei; Peipei Chen; Limei Zhou (European Journal of Clinical Pharmacology, 2024)

Influence of Damping Plate Size on Pitch Motion Response of Floating Offshore Wind Turbine - Jie Xu; Chuansheng Wang; Jiawen Li; Yichen Jiang; Guangyin Tang; Yi Yang (Journal of Marine Science and Engineering, 2024)
For floating offshore wind turbines, a significant pitch and roll motion response of the platform can affect the acceleration and power generation of the nacelle. The damping plate is considered a type of attachment that can be used to reduce rotational motion, but research on its anti-rotational effect is limited. The objective of this work is to analyze the impact of installing damping plates and varying their sizes on the pitch motion response of semi-submersible platforms, while also proposing optimization strategies for damping plate design. Firstly, a comparison between numerical simulations and experimental measurements validates the accuracy of the CFD calculations. Subsequently, different sizes of damping plates are proposed for the platforms, followed by simulations under various conditions. Finally, comprehensive data analysis is conducted. The findings suggest that installing damping plates enhances both the platform’s added moment of inertia and damping coefficients while simultaneously amplifying its motion response in regular waves. Furthermore, increasing the size of damping plates leads to an increase in both the added moment of inertia and motion response for the platform, whereas the damping coefficient exhibits an initial increasing trend followed by a subsequent decrease. Ultimately, it is found that increasing the distance between damping plates and the free surface significantly reduces wave-induced loads on the platform.

Developing thermal prediction models for children in outdoor environments - Yichen Li; Xiaoxi Wang; Jiaqi Li; Chen Shi; Bo Hong (Sustainable Cities and Society, 2024)

Lightweight, high-strength and fireproof borax-crosslinked graphene/hydroxyethyl cellulose hybrid aerogels fabricated via ice template method - Junjiao Li; Chao Sui; Chenxi Zhao; Gong Cheng; Zifu Zang; Lei Wen; Yuna Sang; Yichen Zhou; Yushun Zhao; Xin Yan; Xiaodong He; Chao Wang (Chemical Engineering Journal, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Sustainable control of organic-inorganic combined fouling of electroactive ultrafiltration membrane during electrocatalytic-driven self-cleaning process: Mechanism and implications - Kaiyue Tian; Xinxin Xu; Zhonglong Yin; Yulong Liu; Yichen Zhu; Feilong Li; Tiancheng Wen; Weiben Yang (Journal of Water Process Engineering, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

The occurrence of selected organic pollutants in the soils of the Songnen Plain, China - Yanan Chen; Yichen Zhang; Jiquan Zhang; Chenyang Wu; Li Li; Qiuling Lang; Huanan Liu (Journal of Soils and Sediments, 2024)

Effects of Potassium Fertilizer Base/Topdressing Ratio on Dry Matter Quality, Photosynthetic Fluorescence Characteristics and Carbon and Nitrogen Metabolism of Potato - Jiali Xie; Ming Li; Mingfu Shi; Yichen Kang; Ruyan Zhang; Yong Wang; Weina Zhang; Shuhao Qin (Potato Research, 2024)

Evaluation of immunogenicity and protective efficacy of outer membrane vesicles from Salmonella Typhimurium and Salmonella Choleraesuis - Yichen Tian; Shan Huang; Guodong Zhou; Xia Fei; Yu-an Li; Quan Li; Shifeng Wang; Huoying Shi (Veterinary Microbiology, 2024)

Soil moisture regulates soil-microbe-enzyme stoichiometries during recovery succession in patchily degraded alpine meadows on the Qinghai-Tibet Plateau - Yu Chai; Xilai Li; Chengyi Li; Yunqiao Ma; Zihan Song; Pei Gao; Yichen Ba; Weidong Wei (Ecological Engineering, 2024)

Confinement effect of FeMOFs glass enhances the proton coupled electron transfer reaction for the organic pollutants polymerization toward sustainable water purification - Shiyu Zuo; Yichen Ding; Haoshan Cheng; Zeyu Guan; Xiaohu Li; Dongya Li (Chemical Engineering Journal, 2024)

Layer-by-layer fabrication of alginate/polyethyleneimine multilayer on magnetic interface with enhanced efficiency in immuno-capturing circulating tumor cells - Yang Xiao; Zhiyi Zhou; Yifan Zuo; Xueyuan Wu; Yuping Liu; Yichen Li; Yuetong Gao; Xiashu Zhang; Yu Wang; Lili Hu; Chenglin Li (Analytica Chimica Acta, 2024)

Realizing high-efficiency thermoelectric module by suppressing donor-like effect and improving preferred orientation in n-type Bi2(Te, Se)3 - Yichen Li; Shulin Bai; Yi Wen; Zhe Zhao; Lei Wang; Shibo Liu; Junqing Zheng; Siqi Wang; Shan Liu; Dezheng Gao; Dongrui Liu; Yingcai Zhu; et al. (Science Bulletin, 2024)

Phylogenomics of Afrotherian mammals and improved resolution of extant Paenungulata - Gaoming Liu; Qi Pan; Yichen Dai; Xiao Wang; Meng Li; Pingfen Zhu; Xuming Zhou (Molecular Phylogenetics and Evolution, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Environmental temperature variations drive the changes of microbial communities to affect Baijiu flavor quality: Case study of Qingxiangxing Baijiu - Qiao Huang; Ying Liu; Zongjun He; Yichen Mao; Hui Wu; Lei Tian; Shuangquan Xiang; Liuzhu Long; Yang Li; Tongwei Guan (Food Bioscience, 2024)

Unlocking Wheat's Heat Stress Survival Secrets: A Comprehensive Study of Spike Development’s Metabolic Responses - Junjie Han; Wenjing Wang; Yichen Liu; Yiting Shen; Weihua Li (Journal of Plant Growth Regulation, 2024)

Effects of wind speed on performance of a novel forced-air ice slurry wet precooling system - Yichen Huang; Weidong Wu; Min Li; Xiang Li; Hua Zhang (International Journal of Refrigeration, 2024)

Efficient structure from motion for UAV images via anchor-free parallel merging - San Jiang; Yichen Ma; Wanshou Jiang; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Phospho-Enriched amidoxime adsorbents utilizing synergistic multifunctional groups for enhanced uranium removal from wastewater - Fuan Lei; Yun Zhou; Long Geng; Binliang Li; Junxian Chen; Yuankun Liu; Yichen Hu; Tonghuan Liu; Keliang Shi; Wangsuo Wu; Junqiang Yang (Chemical Engineering Journal, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

miR-377-3p Regulates Hippocampal Neurogenesis via the Zfp462-Pbx1 Pathway and Mediates Anxiety-Like Behaviors in Prenatal Hypoxic Offspring - Bin Wang; Yichen Zhu; Bin Wei; Hongtao Zeng; Pengjie Zhang; Lingjun Li; Hongyan Wang; Xiaohui Wu; Yufang Zheng; Miao Sun (Molecular Neurobiology, 2024)

To live or die: “Fine-tuning” adaptation revealed by systemic analyses in symbiotic bathymodiolin mussels from diverse deep-sea extreme ecosystems - Jianzhou Xu; Ruoxuan Zhao; Ao Liu; Liya Li; Shuimei Li; Yichen Li; Mengjie Qu; Yanan Di (Science of The Total Environment, 2024)

Optimization of mooring systems for a 10MW semisubmersible offshore wind turbines based on neural network - Yichen Jiang; Yingjie Duan; Jiawen Li; Mingsheng Chen; Xiaoming Zhang (Ocean Engineering, 2024)

Ultrafast and selective capture of 99TcO4-/ReO4- from wastewater by hyper-branched quaternary ammonium group-functionalized resin - Juan Tong; Junqiang Yang; Xiaobo Li; Kesheng Hu; Yiman Lu; Man Wang; Yichen Hu; Keliang Shi (Journal of Hazardous Materials, 2024)

Chameleon-inspired structural coloration of textiles with non-close-packed photonic crystals for high color saturation and color fastness - Xiaohui Wang; Xiaohui Liang; Yichen Li; Xinyang Li; Guojin Liu; Mingan Hu; Yijia Liu; Yi Huang; Lan Zhou; Wenlong Zhou; Jianzhong Shao (Chemical Engineering Journal, 2024)

GhHB14_D10 and GhREV_D5, two HD-ZIP III transcription factors, play a regulatory role in cotton fiber secondary cell wall biosynthesis - Shuaijie Li; Mengli Yu; Ghulam Qanmber; Mengru Feng; Ghulam Hussain; Yichen Wang; Zuoren Yang; Jie Zhang (Plant Cell Reports, 2024)

The effects of atmospheric nitrogen deposition in coral-algal phase shifts on remote coral reefs - Yichen Fu; Xiaoyan Chen; Yuchen Liu; Yuxiao Li; Kefu Yu (Frontiers in Marine Science, 2024)
Remote seawater has been considered a potential refuge for corals in the face of anthropogenic disturbances. However, these remote areas may receive increased atmospheric N deposition, and the ecological consequences remain unclear. This field survey revealed coral-algal phase shifts in the mid-north of the South China Sea. These shifts were observed in 44%, 13.6%, and 26.5% of the sampled reef sites at depths of 1-4 m, 5-8 m, and 10-15 m, respectively. Over 50% of sections in the deeper depths hosted fewer corals compared to shallower areas, coinciding with a higher abundance of macroalgae in the deeper layers. Furthermore, based on long-term observation of atmospheric N flux, laboratory experiments were conducted to explore the cause of coral declines. The results indicate that N supply efficiently promoted macroalgae growth. The saturation of N absorption by macroalgae occurred within 2 weeks, leading to nutrient accumulation in seawater, especially nitrate, which had a direct impact on corals. While moderate N fluxes appeared to mitigate coral bleaching, high N fluxes, even with a balanced P supply or medium level of nutrients with an imbalanced N/P ratio, can both increase the susceptibility of corals to heat bleaching. This study explains the coral-algal phase shift in remote and relatively deep seawater and improves understanding of the cause-and-effect relationship between atmospheric N deposition and coral reef decline.

Development of a dual-functional inhibitor for natural gas hydrates and construction of drilling fluid system - Jintang Wang; Zhijun He; Yichen Yan; Lei Liu; Jin Yan; Bo Liao; Ke Zhao; Yiyao Li; Longqiao Chen (Gas Science and Engineering, 2024)

Pyrolysis behavior of tar-rich coal with various coal-forming environments: A TGA and in-situ transmission FTIR study - Qingmin Shi; Yichen Mi; Shuangming Wang; Yue Cai; Ruijun Ji; Weifeng Xue; Xin Li; Bo Han (Fuel, 2024)

Exploring building component thermal storage performance for optimizing indoor thermal environment – A case study in Beijing - Yichen Han; Zhengnan Zhou; Wenwen Li; Jiajia Feng; Chaohong Wang (Energy and Buildings, 2024)

Matchable image retrieval for large-scale UAV images: an evaluation of SfM-based reconstruction - Junhuan Liu; Yichen Ma; San Jiang; Lizhe Wang; Qingquan Li; Wanshou Jiang (International Journal of Remote Sensing, 2024)

Time-Lapse Macro Imaging with Dissolution Tests for Exploring the Interrelationship Between Disintegration and Dissolution Behaviors of Solid Dosages - Yichen Yang; Jiajia Gengji; Tao Gong; Zhirong Zhang; Li Deng (Pharmaceutical Research, 2024)

Cellular and Molecular Roles of Immune Cells in the Gut-Brain Axis in Migraine - Yichen Zhou; Miaoyi Pang; Yiran Ma; Lingling Lu; Jiannan Zhang; Peipei Wang; Qian Li; Fei Yang (Molecular Neurobiology, 2024)

Examination of the relationship of carbonate alkalinity stress and ammonia metabolism disorder-mediated apoptosis in the Chinese mitten crab, Eriocheir sinensis: Potential involvement of the ROS/MAPK signaling pathway - Shengqiang Tao; Xiaojing Li; Jingyao Wang; Yichen Bai; Jiahao Wang; Yuhong Yang; Zhigang Zhao (Aquaculture, 2024)

Environment-relevant concentrations of cadmium induces necroptosis and inflammation; baicalein maintains gill homeostasis through suppressing ROS/ER stress signaling in common carps (Cyprinus carpio L.) - Xiaojing Li; Qian Wu; Dan Chen; Yichen Bai; Yuhong Yang; Shiwen Xu (Environmental Pollution, 2024)

Impact of outdoor microclimate on the performance of high-rise multi-family dwellings in cold areas and optimization of building passive design - Wenwen Li; Zhengnan Zhou; Chaohong Wang; Yichen Han (Building and Environment, 2024)

Disrupted morphological brain network organization in subjective cognitive decline and mild cognitive impairment - Yuxin Chen; Lingyan Liang; Yichen Wei; Ying Liu; Xiaocheng Li; Zhiguo Zhang; Linling Li; Demao Deng (Brain Imaging and Behavior, 2023)

Study on Mooring Design of 15 MW Floating Wind Turbines in South China Sea - Mingsheng Chen; Jiale Jiang; Wei Zhang; Chun Bao Li; Hao Zhou; Yichen Jiang; Xinghan Sun (Journal of Marine Science and Engineering, 2023)
Wind turbines and floating platform upsizing are major trends in the current offshore wind development. However, harsh environmental conditions increase the risk of anchor dragging and mooring failure when deploying large offshore floating wind turbines. Therefore, it is necessary to design a mooring system for the specific deployment site. This study aims to perform the mooring system design of a floating offshore wind turbine (FOWT) operated in the South China Sea, which is a combination of the IEA 15 MW wind turbine and UMaine VolturnUS-S floating platform. Hydrodynamic coefficients were calculated based on the potential flow theory, considering the environmental loads in the South China Sea. Additionally, the hydrodynamic coefficients were imported into AQWA to calculate the time-domain mooring tension. The mooring design parameters, such as mooring line length, nominal sizes, and anchor point, were determined using the criterion of anchor uplift, maximum breaking strength, and fatigue life, respectively. The design criterion required that the anchor uplift is not more than the allowable value, the long-term breaking limit of mooring with a 100-year return period should be less than the maximum breaking limit, and the fatigue damage accumulation in 50 years should be safe. The mooring design procedure provides a reference for mooring system design and safe operation of large floating wind turbines in the South China Sea.

Influence of Natural Gas Hydrate Distribution Patterns on the Macroscale–Mesoscale Mechanical Properties of Hydrate-Bearing Sediments - Yujing Jiang; Xiaoyu Du; Peng Yan; Meng Li; Hengjie Luan; Xianzhuang Ma; Yichen Shi (Journal of Marine Science and Engineering, 2023)
Studying the mechanical characteristics of hydrate-bearing sediments (HBS) contributes to the comprehensive understanding of the mechanical behavior in environments with natural gas hydrate (NGH) occurrences. Simultaneously, the distribution patterns of hydrates significantly influence the strength, deformation, and stability of HBS. Therefore, this paper employs particle flow code (PFC) to conduct biaxial discrete element simulations on specimens of HBS with different hydrate distribution patterns, revealing the macroscale–mesoscale mechanical properties, evolution patterns, and destructive mechanisms. The results indicate that the strain-softening behavior of HBS specimens strengthens with the increase in hydrate layer thickness, leading to higher peak strength and E50 values. During the gradual movement of the hydrate layer position (Ay) from both ends to the center of the specimen (Ay = 0.40 mm → Ay = 20 mm), the strain-softening behavior weakens. However, when Ay = 20 mm, the specimen exhibits evident strain-softening behavior again. Moreover, with an increase in the angle between the hydrate layer and the horizontal direction (α) greater than 20°, the peak strength of the specimen increases, while E50 shows an overall decreasing trend. The influence of axial loads on the hydrate layer in specimens varies with α, with larger contact forces and fewer cracks observed for higher α values.

Leucobacter edaphi sp. nov., a highly chromate-tolerant bacterium isolated from chromium containing chemical plant soil - Bijun Zheng; Zhe Xu; Li Yang; Guangyang Jiang; Jia Chen; Yichen Yang; Yongqiang Tian (Antonie van Leeuwenhoek, 2023)

Efficient degradation of phenanthrene by biochar-supported nano zero-valent iron activated persulfate: performance evaluation and mechanism insights - Lai Zhou; Yichen Wang; Danqiong Li; Jiehui Zhang; Xueqiang Zhu (Environmental Science and Pollution Research, 2023)

Boosting CO2 electroreduction to ethanol through abundant grain boundaries in In2S3 nanostructures - Yichen Meng; Minglu Li; Yihan Xu; Hai Liu; Siyu Kuang; Sheng Zhang; Xinbin Ma (Chemical Engineering Journal, 2023)

Electroacupuncture Inhibits Pain Memory and Related Anxiety-Like Behaviors by Blockading the GABAB Receptor Function in the Midcingulate Cortex - Xiaoyu Li; Yichen Zhu; Haiju Sun; Zui Shen; Jing Sun; Siqi Xiao; Xiaofen He; Boyu Liu; Yifang Wang; Yuxin Hu; Boyi Liu; Yi Liang; et al. (Molecular Neurobiology, 2023)
Pain memory is commonly considered an underlying cause of chronic pain and is also responsible for a range of anxiety. Electroacupuncture (EA) has been shown to ameliorate pain memories and exert anti-anxiety effects. Previous research has indicated that GABAergic neurons and/or GABA receptors (GABARs) in the midcingulate cortex (MCC) have potential associations with chronic pain and anxiety. However, there is no known empirical research that has specifically studied the effects of EA on the GABAergic system in the MCC. Here, we used cross-injection of carrageenan to establish the pain memory rats model. Immunofluorescence were used to detect the excitability of GABAergic neurons within MCC. Von Frey filament, elevated zero maze, and open field tests were used to measure mechanical allodynia and anxiety-like behaviors, combined with chemogenetic and pharmacologic technologies. Finally, this study provides evidence that pain memories contribute to generalized negative emotions and that downregulating the activity of GABAergic neurons within MCC could block pain memories and reverse anxiety emotion. Specifically, GABA B R is involved in pain memory and related anxiety-like behaviors. Activation of GABAergic neurons in the MCC did not reverse the effects of EA on pain memories and related anxiety-like behaviors, whereas these effects could be reversed by a GABA B R agonist. These findings highlight the functional significance of GABA B R in the EA-mediated attenuation of pain memories and related anxiety-like behaviors in rats.

Heterogeneous activation of permonosulfate by biochar supporting CuCoFe layered double hydroxide for rapid degradation of phenanthrene - Lin Wu; Tao Jin; Dan Li; Liping Wang; Yichen Sun (Journal of Environmental Chemical Engineering, 2023)

Study on initiation characteristics of oblique detonation induced by hydrogen jets in acetylene-air mixtures - Zhang Yichen; Xiang Gaoxiang; Gao Xiang; Yu Jia; Hu Xiquan; Xin Yirong; Li Danyang; Wang Qiu (Fuel, 2023)

Infrared Imageries of Human Body Activated by Tea Match the Hypothesis of Meridian System - Wenli Jin; Yichen Tao; Chen Wang; Lufei Wang; Xue Ao; Mingjie Su; Binwei Hu; Yuxiao Ouyang; Jiaxing Liu; Hui Li (Phenomics, 2023)

Camouflaging multifunctional nanoparticles with bacterial outer membrane for augmented chemodynamic/photothermal/starvation/chemo multimodal synergistic therapy of orthotopic glioblastoma - Yichen He; Yi Pan; Xin Zhao; Luyi Ye; Longcai Liu; Wenliang Wang; Meng Li; Dapeng Chen; Yu Cai; Xiaozhou Mou (Chemical Engineering Journal, 2023)

Genetic analysis of stripe rust resistance in the common wheat line Kfa/2*Kachu under a Chinese rust environment - Yuruo Yin; Chan Yuan; Yichen Zhang; Shunda Li; Bin Bai; Ling Wu; Yong Ren; Ravi P. Singh; Caixia Lan (Theoretical and Applied Genetics, 2023)

Effects of Nitrogen, Phosphorus and Potassium Combined Fertilisation on the Dry Matter Accumulation, Distribution and Yield of Potato Under Ridge and Furrow Film Mulch Cropping - Hong Li; Xinyu Yang; Yichen Kang; Wenlin Li; Haojun Li; Shuhao Qin (Potato Research, 2023)

Partial Substitution of Chemical Fertilizer with Organic Manure Enhances Yield Attributes and Tuber Quality in Potato - Mingfu Shi; Aixia Guo; Yichen Kang; Weina Zhang; Yanling Fan; Xinyu Yang; Ruyan Zhang; Yong Wang; Yajie Li; Shuhao Qin (Journal of Soil Science and Plant Nutrition, 2023)

Acaricidal and repellent activities of ethanol extracts of nine chinese medicinal herbs against Rhipicephalus microplus (Acari: Ixodidae) - Donglinag Li; Shunli Lu; Yichen Jian; Shuqi Cheng; Qianming Zhao; Huizhen Yuan; Nanhao Wang; Yufeng Liu; Sumei Zhang; Longxian Zhang; Rongjun Wang; Fuchun Jian (Experimental and Applied Acarology, 2023)
Rhipicephalus microplus is a major threat to the cattle industry worldwide. The intensive use of acaricides and repellents has resulted in drug resistance. Hence, effective and eco-friendly pest control alternatives are urgently needed, especially from natural plant resources. In this study, the acaricidal and repellent activities of nine herbs against the larvae and eggs of R. microplus were evaluated. The results showed that ethanol extracts of star anise ( Illicium verum ), chaulmoogra ( Hydnocarpus anthelmintica ), motherwart ( Leonurus artemisia ), mandarin orange peel (citri reticulatae pericarpium, i.e., peel of Citrus reticulata fruit), and stemona ( Stemona sessilifolia ) had good contact acaricidal activities of 100, 98, 94, 88 and 86%, respectively, whereas star anise and clove ( Syzygium aromaticum ) had good fumigant acaricidal activities of 98 and 96%, respectively. The hatching inhibition rate of star anise against R. microplus eggs was 100%. All nine herbs had good real-time repellent rates, but only castor bean and star anise had repellent effects after 48 h (81.3 and 79.6%, respectively). This is the first report of the acaricidal and repellent activities of these medicinal herbs against R. microplus . Ethanol extracts of these herbs might be considered as potential alternatives to chemical acaricides for control of R . microplus .

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Baicalin suppressed necroptosis and inflammation against chlorpyrifos toxicity; involving in ER stress and oxidative stress in carp gills - Xiaojing Li; Yichen Bai; Yanju Bi; Qian Wu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Dual photoelectrodes activate oxygen evolution and oxygen reduction reactions enabling a high-performance Zn-air battery and an efficient solar energy storage - Jia You; Bingqing Zhang; Xianlong Wang; Haoran Zhang; Lanlan Huang; Lihua He; Nanxin Li; Yichen Chang; Shiwei Lin (Chemical Engineering Journal, 2023)

Role of Tim-3 in COVID-19: a potential biomarker and therapeutic target - Haodong Ma; Shengju Ren; Qingpeng Meng; Boyuan Su; Kun Wang; YiChen Liu; Junpeng Wang; Degang Ding; Xin Li (Archives of Virology, 2023)

Insights into heavy metals shock on anammox systems: Cell structure-based mechanisms and new challenges - Yichen Wu; Yingxin Zhao; Yinuo Liu; Jiaojiao Niu; Tianyang Zhao; Xinhao Bai; Arif Hussain; Yu-You Li (Water Research, 2023)

Effects of outrigger configuration on trimaran stability in longitudinal waves - Yichen Jiang; Mingzhe Wang; Junyu Bai; Yuan Sun; Jiawen Li (Ocean Engineering, 2023)

A hyaluronic acid modified cuprous metal-organic complex for reversing multidrug resistance via redox dyshomeostasis - Yichen Wan; Zelong Chen; Yi Wang; Wenkang Zhao; Zhichao Pei; Liang Pu; Yinghua Lv; Jiaxuan Li; Jiahui Li; Yuxin Pei (Carbohydrate Polymers, 2023)

Efficient removal of U(Ⅵ) by an environmental-friendly amidoxime matrix microspheres: Batch experiments and mechanism investigation - Tonghuan Liu; Jiaju Ma; Xiaobo Li; Yun Zhou; Yichen Hu; Fuan Lei; Keliang Shi; Qunyan Wu; Junqiang Yang (Journal of Environmental Chemical Engineering, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

Ar-turmerone suppresses Aspergillus flavus growth and aflatoxin accumulation: Finding a new antifungal agent based on stored maize - Zheyu Li; Yanan Sun; Linghui Gu; Yuchi Wang; Mingqin Xu; Yunhao Zhou; Yichen Hu; Wenbo Ma (Food Research International, 2023)

Identification and evaluation of potential probiotics against skin-ulceration disease in the Chinese tongue sole (Cynoglossus semilaevis) - Zhihan Zuo; Bijiao Shang; Hongrui Liu; Jiacheng Sun; Wenyue Li; Yichen Liu; Jinsheng Sun (Fish & Shellfish Immunology, 2023)

Relationships between EEG and thermal comfort of elderly adults in outdoor open spaces - Xiaoyan Ma; Lin Song; Bo Hong; Yichen Li; Yang Li (Building and Environment, 2023)

A viscosity equivalent reduced-order method and its application to ship roll prediction - Yichen Jiang; Yu Dong; Peng Li; Hongyun Zong; Jiawen Li (Ocean Engineering, 2023)

Dynamic response analysis of a floating vertical axis wind turbine with helical blades based on the model test - Wanru Deng; Ying Guo; Liqin Liu; Yan Li; Yichen Jiang; Peng Xie (Ocean Engineering, 2023)

Global/local buckling analysis of thin-walled I-section beams via hierarchical one-dimensional finite elements - Yichen Yang; Yanchuan Hui; Ping Li; Jie Yang; Qun Huang; Gaetano Giunta; Salim Belouettar; Heng Hu (Engineering Structures, 2023)

An actual-performance-oriented study on the relationship between environmental efficiency and passive design factors for multi-family dwellings in cold areas - Wenwen Li; Zhengnan Zhou; Yichen Han (Energy and Buildings, 2023)

Production of 1,3-propanediol using enzymatic hydrolysate derived from pretreated distillers' grains - Li Yang; Guangyang Jiang; Jia Chen; Zhe Xu; Yichen Yang; Bijun Zheng; Yi Yang; He Huang; Yongqiang Tian (Bioresource Technology, 2023)

Spatiotemporal variations in meteorological influences on ambient ozone in China: A machine learning approach - Tao Li; Yichen Lu; Xunfei Deng; Yu Zhan (Atmospheric Pollution Research, 2023)

Application of a novel Ca-Fe-Si-S composite for the synchronous stabilization of As, Zn, Cu, and Cd in acidic arsenic slag - Ge Zhang; Huifen Yang; Xuan Li; Yichen Zhou; Song Guo; Tong Zhao (Environmental Science and Pollution Research, 2023)

Revealing the synergistic mechanism of the generation, migration and nearby utilization of reactive oxygen species in FeOCl-MOF yolk-shell reactors - Shiyu Zuo; Yichen Ding; Li Wu; Fan Yang; Zeyu Guan; Su Ding; Dongsheng Xia; Xiaohu Li; Dongya Li (Water Research, 2023)

Variation of molecular structures affecting tar yield: A comprehensive analysis on coal ranks and depositional environments - Qingmin Shi; Chunhao Li; Shuangming Wang; Ruijun Ji; Weifeng Xue; Yichen Mi; Shengquan Wang; Yue Cai (Fuel, 2023)

Multiple effects of visual-acoustic-thermal perceptions on the overall comfort of elderly adults in residential outdoor environments - Meng Du; Bo Hong; Chujian Gu; Yichen Li; Yayun Wang (Energy and Buildings, 2023)

Pyrolysis kinetics and thermodynamic parameters of bamboo residues and its three main components using thermogravimetric analysis - Yingkai Li; Yichen Wang; Meiyun Chai; Chong Li; Nishu; Dominic Yellezuome; Ronghou Liu (Biomass and Bioenergy, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Evaluation of chemical composition, antioxidant activity, and gut microbiota associated with pumpkin juice fermented by Rhodobacter sphaeroides - Yaqin Wang; Lingjia Fan; Jintao Huang; Jingjing Liang; Xingnan Wang; Yichen Ren; Hongcai Li; Tianli Yue; Zhenpeng Gao (Food Chemistry, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

A field test scrutiny on bearing mechanism of super-long bored piles in deep fine silty sand layers - Xinquan Wang; Yichen Que; Kangyu Wang; Hongguo Diao; Yunliang Cui; Qing Li (Marine Georesources & Geotechnology, 2023)

Hippo Signaling Regulates Blastema Formation During Limb Regeneration in Chinese Mitten Crab (Eriocheir sinensis) - Yiran Wang; Xinrui Huang; Qiao Zhou; Yuxin Tian; Jinmei Zuo; Zengzhi Yuan; Yichen Liu; Ju Li; Jinsheng Sun (Marine Biotechnology, 2023)

Rational construction and understanding the effect of metal cation substitution of three novel ternary Zn-Co–Ni-LDHs from 2D to 3D and its enhanced adsorption properties for MO - Zhu Jie; Jiang Yichen; Li Ping; Li Yang; Tian Huiyuan; Du Xiuhong; Wang Zehua; Duan Xianying; Li Chunguang; Cui Jiehu (Environmental Science and Pollution Research, 2023)

Spatio‐temporal changes in the speed of canopy development and senescence in temperate China - Shilong Piao; Jiawei Wang; Xiangyi Li; Hao Xu; Yichen Zhang (Global Change Biology, 2022)
China has been suggested to be the country with the largest vegetation greenness over the last four decades. In this study, we investigated the change in the speed of canopy development and senescence as well as its linkage with climate at monthly scale across temperate China, using satellite‐derived Normalized Difference Vegetation Index (NDVI) data from 1982 to 2015. A significant increase in mean monthly NDVI occurred across all growing‐season months except June and November, but this greening trend was mainly contributed by the faster speed of canopy development in April and the slower speed of canopy senescence in October. The average of V NDVI (the difference in NDVI between 2 consecutive months) over temperate China is significantly increased only in April (7.75 × 10 −4 year −1 , p −4 year −1 , p V NDVI in November is significantly decreased, indicating an increasing trend in the magnitude of leaf fall in the last month of the growing season due to both increase in season maximum greenness and slower canopy senescence in October. We also found clear seasonal differences in the correlations between V NDVI and climatic factors, especially temperature. In April and October, the correlations between V NDVI and temperature were generally positive, while they were negative in June. V NDVI in spring (early growing season) and summer (middle growing season) was also positively correlated with precipitation in semiarid regions. Such seasonally distinct climatic controls on V NDVI should be considered in modelling vegetation responses to climate change. Overall, our findings can help quantify the contribution of different climatic drivers on the shifts in canopy development and senescence and better elucidate the change in vegetation greenness under future climate change.

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

Role of Intraseasonal Oscillation in a Compound Drought and Heat Event over the Middle of the Yangtze River Basin during Midsummer 2018 - Chuhan Lu; Yichen Shen; Yonghua Li; Bo Xiang; Yujing Qin (Journal of Meteorological Research, 2022)

Discrete Element Simulation of the Macro-Meso Mechanical Behaviors of Gas-Hydrate-Bearing Sediments under Dynamic Loading - Yujing Jiang; Meng Li; Hengjie Luan; Yichen Shi; Sunhao Zhang; Peng Yan; Baocheng Li (Journal of Marine Science and Engineering, 2022)
Under the action of dynamic loadings such as earthquakes and volcanic activities, the mechanical properties of gas-hydrate-bearing sediments will deteriorate, leading to a decrease in the stability of hydrate reservoirs and even inducing geological disasters such as submarine landslides. In order to study the effect of dynamic loading on the mechanical properties of hydrate sediments, triaxial compression tests of numerical specimens were carried out by using particle flow code (PFC2D), and the macro-meso mechanical behaviors of specimens were investigated. The results show that the loading frequency has a small effect on the stiffness of the hydrate sediment, while it has a large effect on the peak strength. The peak strength increases and then decreases with the increase in loading frequency. Under the same loading frequency, the peak strength of the hydrate sediment increases with the increase in loading amplitude, and the stiffness of the specimen decreases with the increase in loading amplitude. The maximum shear expansion of the specimen changes with the movement of the phase change point and the rearrangement of the particles. The maximum shear expansion of the specimen changes with the movement of the phase change point and the change of the bearing capacity of the particles after the rearrangement, and the more forward the phase change point is, the stronger the bearing capacity of the specimen in the plastic stage. The shear dilatancy angle and the shear dilatancy amount both increase linearly with the increase in loading amplitude. The influence of loading frequency and amplitude on the contact force chain, displacement, crack expansion, and the number of cementation damage inside the sediment is mainly related to the average axial stress to which the specimen is subjected, and the number of cracks and cementation damage of the sediment specimen increases with the increase in the average axial stress to which the sediment specimen is subjected. As the rate of cementation damage increases, the distribution of shear zones becomes more obvious.

Intranasal Salvinorin A Improves Long-term Neurological Function via Immunomodulation in a Mouse Ischemic Stroke Model - Dilidaer Misilimu; Wei Li; Di Chen; Pengju Wei; Yichen Huang; Sicheng Li; John Grothusen; Yanqin Gao (Journal of Neuroimmune Pharmacology, 2022)
Salvinorin A (SA), a highly selective kappa opioid receptor agonist, has been shown to reduce brain infarct volume and improve neurological function after ischemic stroke. However, the underlying mechanisms have not been fully understood yet. Therefore, we explored whether SA provides neuroprotective effects by regulating the immune response after ischemic stroke both in the central nervous system (CNS) and peripheral circulation. In this study, adult male mice were subjected to transient Middle Cerebral Artery Occlusion (tMCAO) and then were treated intranasally with SA (50 μg/kg) or with the vehicle dimethyl sulfoxide (DMSO). Multiple behavioral tests were used to evaluate neurofunction. Flow cytometry and immunofluorescence staining were used to evaluate the infiltration of peripheral immune cells into the brain. The tracer cadaverine and endogenous immunoglobulin G (IgG) extravasation were used to detect blood brain barrier leakage. We observed that SA intranasal administration after ischemic stroke decreased the expression of pro-inflammatory factors in the brain. SA promoted the polarization of microglia/macrophages into a transitional phenotype and decreased the pro-inflammatory phenotype in the brain after tMCAO. Interestingly, SA treatment scarcely altered the number of peripheral immune cells but decreased the macrophage and neutrophil infiltration into the brain at 24 h after tMCAO. Furthermore, SA treatment also preserved BBB integrity, reduced long-term brain atrophy and white matter injury, as well as improved the long-term neurofunctional outcome in mice. In this study, intranasal administration of SA improved long-term neurological function via immuno-modulation and by preserving blood–brain barrier integrity in a mouse ischemic stroke model, suggesting that SA could potentially serve as an alternative treatment strategy for ischemic stroke. Graphic Abstract

Adiantic acid, a new unsaturated fatty acid with a cyclopropane moiety from Adiantum flabellulatum L. - Junping Chen; Yichen Li; Jianguo Cao; Jinwen Huang; Can Jiang; Xiling Dai; Guozheng Huang (Natural Product Research, 2022)

Evaluation of the in vitro acaricidal activity of ethanol extracts of seven Chinese medicinal herbs on Ornithonyssus sylviarum (Acari: Macronyssidae) - Yichen Jian; Shijie Li; Dongliang Li; Changshen Ning; Sumei Zhang; Fuchun Jian; Hongbin Si (Experimental and Applied Acarology, 2022)
Ornithonyssus sylviarum (Acari: Macronyssidae) is a common ectoparasite that feeds on the blood of poultry. Following infestation, this mite will cause symptoms such as weight loss, anemia, and decreased egg production. To explore green and safe drugs for the prevention and treatment of O. sylviarum , this study evaluated the effects of ethanol extracts of seven Chinese medicinal herbs— Leonurus artemisia (motherwort), Illicium verum (star anise), Cinnamomum cassia (cinnamon), Hibiscus syriacus , Artemisia argyi (Chinese mugwort), Taraxacum sp. (dandelion), and Syzygium aromaticum (clove)—on O. sylviarum at different life stages. The results showed that different methods of administration affected the acaricidal efficacy of these plant extracts on O. sylviarum . After 6 h of administration with the fumigation method, the acaricidal efficacy of S. aromaticum on adults, nymphs and larvae of O. sylviarum reached 100%. 30 min after administration with the infiltration method, S. aromaticum , H. syriacus and L. artemisia showed acaricidal effects on adults and nymphs of O. sylviarum reaching 100%. In another experiment evaluating the inhibition of egg hatching of O. sylviarum with alcohol extracts of these seven herbs, at 48 h after treatment, A. argyi and C. cassia showed inhibition rates of 19.4%. The results of this study indicate that S. aromaticum induced mortality at all stages of O. sylviarum , whereas A. argyi was found to be the most effective at inhibiting the mite’s egg hatching among the seven herbs. These herbs can therefore be used as potential substitutes for chemical pesticides to prevent and control O. sylviarum . These results provide practical knowledge for the control of O. sylviarum .

Characteristics of an ore-controlling shear zone in the Cigou-Zaoyang gold mine area of Ankang, South Qinling Mountains, China - Hujun He; Yichen Zhao; Jian Zhang; Xingke Yang; Rui Xing; Wei Li (Arabian Journal of Geosciences, 2022)

Experimental study on the physico-mechanical properties and temperature field evolution of granite subjected to different heating–cooling treatments - Zhongrui Zhao; Yaoqing Hu; Peihua Jin; Yichen Xu; Yuefei Hu; Chun Li; Qiaorong Meng (Bulletin of Engineering Geology and the Environment, 2021)

Effects of ultrasound on functional properties, structure and glycation properties of proteins: a review - Derong Lin; Qiuting Zhang; Lijuan Xiao; Yichen Huang; Zhengfang Yang; Zhijun Wu; Zongcai Tu; Wen Qin; Hong Chen; Dingtao Wu; Qing Zhang; Suqing Li (Critical Reviews in Food Science and Nutrition, 2021)

Cloning and characterization of the DIR1 promoter from Eucommia ulmoides Oliv and its response to hormonal and abiotic stress - Ziyun Li; Biao Li; Yichen Zhao; De-gang Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Combining ability and genetic diversity under low-temperature conditions at germination stage of maize (Zea mays L.) - Jiayue Zhang; Yichen Li; Ziwen Zhang; Hong Di; Lin Zhang; Xuerui Wang; Zhenhua Wang; Yu Zhou (Euphytica, 2021)

Characteristics of Slamming Pressure and Force for Trimaran Hull - Zhe Sun; Xupeng Sui; Yanzeng Deng; Li Zou; A. Korobkin; Lixin Xu; Yichen Jiang (Journal of Marine Science and Engineering, 2021)
In this paper, the characteristics of the impact pressure and force of a trimaran section was studied by Computational Fluid Dynamics (CFD). The time domain features of the slamming pressure or force showed a strong correlation with the penetration depth regardless of the specific ways of water entry. The effects of velocity and acceleration on the impact pressure and force were analyzed. It was found that the initial impact of the main hull and the wet-deck slamming were predominantly affected by the entry velocities, whilst the acceleration had almost no effect for initial impact. The impact velocity presented a quadratic relation with slamming pressure/forces, and the relation between acceleration and wet-deck slamming pressure/force was linear. These were consistent with the patterns implied by analytical models such as the Wagner or MLM (Modified Logvinovich model) theories.

Impact of Typhoons on Floating Offshore Wind Turbines: A Case Study of Typhoon Mangkhut - Jiawen Li; Jingyu Bian; Yuxiang Ma; Yichen Jiang (Journal of Marine Science and Engineering, 2021)
A typhoon is a restrictive factor in the development of floating wind power in China. However, the influences of multistage typhoon wind and waves on offshore wind turbines have not yet been studied. Based on Typhoon Mangkhut, in this study, the characteristics of the motion response and structural loads of an offshore wind turbine are investigated during the travel process. For this purpose, a framework is established and verified for investigating the typhoon-induced effects of offshore wind turbines, including a multistage typhoon wave field and a coupled dynamic model of offshore wind turbines. On this basis, the motion response and structural loads of different stages are calculated and analyzed systematically. The results show that the maximum response does not exactly correspond to the maximum wave or wind stage. Considering only the maximum wave height or wind speed may underestimate the motion response during the traveling process of the typhoon, which has problems in guiding the anti-typhoon design of offshore wind turbines. In addition, the coupling motion between the floating foundation and turbine should be considered in the safety evaluation of the floating offshore wind turbine under typhoon conditions.

Water Quality Analysis of the Yangtze and the Rhine River: A Comparative Study Based on Monitoring Data from 2007 to 2018 - Xuan Li; Yichen Xu; Mei Li; Rong Ji; Reto Dolf; Xueyuan Gu (Bulletin of Environmental Contamination and Toxicology, 2021)

Degradation of the ciprofloxacin antibiotic by photo-Fenton reaction using a Nafion/iron membrane: role of hydroxyl radicals - Fei Wang; Yichen Zhang; Hao Ming; Li Wang; Zhongyuan Zhao; Yuehong Wang; Jiyan Liang; Yan Qin (Environmental Chemistry Letters, 2020)

Wind Tunnel Test on the Effect of Solidity on Near Wake Instability of Vertical-Axis Wind Turbine - Li Zou; Kun Wang; Yichen Jiang; Aimin Wang; Tiezhi Sun (Journal of Marine Science and Engineering, 2020)
Owing to the rapid development of the offshore wind power technology and increasing capacity of wind turbines, vertical-axis wind turbines (VAWTs) have experienced a great development. Nevertheless, the VAWT wake effect, which affects the power generation efficiency and rotor fatigue life, has not been thoroughly understood. In this study, the mid-span wake measurements on a VAWT in six different configurations were conducted. This study aimed to investigate the effect of solidity on near wake instability of vertical-axis wind turbine. By using the wavelet analysis method to analyse the measured velocity (or pressure) time series signals on a multi-scale and with multi-resolution, the dynamic characteristics of the coherent vortex structures in the wake evolution process were determined. The results show that with increasing solidity, the VAWT wake develops into a bluff body wake mode. In addition, a characteristic frequency that is lower than the low-frequency large-scale vortex shedding frequency occur. The wavelet transform was used to decompose and reconstruct the measured data, and the relationship between the low-frequency large-scale vortex shedding and lower frequency pulsation was established. The results provide important data for numerical modelling and new insights into the physical mechanism of the VAWT wake evolution into a bluff body wake.

Characterizing 40 years of natural Pinus sylvestris var. mongolica carbon stocks in Northeast China using stand age from remote sensing time series - Xiufen Li; Yichen Tian; Xiao Zheng; Junxia Cong; Lining Song (International Journal of Remote Sensing, 2020)

Levo-tetrahydropalmatine Attenuates Neuron Apoptosis Induced by Cerebral Ischemia–Reperfusion Injury: Involvement of c-Abl Activation - Ruoxi Sun; Yichen Song; Shanshan Li; Zhanqiang Ma; Xueyang Deng; Qiang Fu; Rong Qu; Shiping Ma (Journal of Molecular Neuroscience, 2018)

Comparative WGBS identifies genes that influence non-ripe phenotype in tomato epimutant Colourless non-ripening - Weiwei Chen; Zhiming Yu; Junhua Kong; Hui Wang; Yichen Li; Mei Zhao; Xiaohong Wang; Qianqian Zheng; Nongnong Shi; Pengcheng Zhang; Silin Zhong; Paul Hunter; et al. (Science China Life Sciences, 2018)

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)

Lower Cambrian polychaete from China sheds light on early annelid evolution - Jianni Liu; Qiang Ou; Jian Han; Jinshu Li; Yichen Wu; Guoxiang Jiao; Tongjiang He (The Science of Nature, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Detected microsatellite polymorphisms in genetically altered inbred mouse strains - Xiaoyan Du; Jing Cui; Chao Wang; Xueyun Huo; Jing Lu; Yichen Li; Zhenwen Chen (Molecular Genetics and Genomics, 2013)

SNIP1: a new activator of HSE signaling pathway - Qiang Li; Jian An; Xianghua Liu; Mingjun Zhang; Yichen Ling; Chenji Wang; Jing Zhao; Long Yu (Molecular and Cellular Biochemistry, 2012)

Crop classification using multi-configuration SAR data in the North China Plain - Kun Jia; Qiangzi Li; Yichen Tian; Bingfang Wu; Feifei Zhang; Jihua Meng (International Journal of Remote Sensing, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Vegetation classification method with biochemical composition estimated from remote sensing data - Kun Jia; Bingfang Wu; Yichen Tian; Yuan Zeng; Qiangzi Li (International Journal of Remote Sensing, 2011)

Systematic analysis of gene expression level with tissue-specificity, function and protein subcellular localization in human transcriptome - Qiang Li; Xianghua Liu; Quanyuan He; Lei Hu; Yichen Ling; Yanhua Wu; Xianmei Yang; Long Yu (Molecular Biology Reports, 2011)

Characterization of a novel human HMBOX1 splicing variant lacking the homeodomain and with attenuated transcription repressor activity - Mingjun Zhang; Shuai Chen; Qiang Li; Yichen Ling; Jie Zhang; Long Yu (Molecular Biology Reports, 2010)

Characterization of a novel human CDK5 splicing variant that inhibits Wnt/β-catenin signaling - Qiang Li; Xianghua Liu; Mingjun Zhang; Guangming Ye; Qian Qiao; Yichen Ling; Yanhua Wu; Yuanyuan Zhang; Long Yu (Molecular Biology Reports, 2010)

Molecular Cloning and Expression Profile of Putative Antilipopolysaccharide factor in Chinese Shrimp(Fenneropenaeus chinensis) - Fengsong Liu; Yichen Liu; Fuhua Li; Bo Dong; Jianhai Xiang (Marine Biotechnology, 2005)